Curable composition, cured product, and method for producing cured product
By using a combination of active hydrogen compounds with pKa of 10 or less or more than 10 and a cationic catalyst, the curing reactivity of the alicyclic epoxy resin is improved, and the thermoplastic cured product is obtained through linear polymerization, which solves the problems of low curing reactivity of the alicyclic epoxy resin and easy cross-linking of the aromatic epoxy resin cured product, and achieves the effects of rapid curing and high thermoplasticity.
Patent Information
- Application Number
- CN202380061358.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the curing reactivity of the alicyclic epoxy resin is low, resulting in a long curing reaction time when a large amount of alicyclic epoxy resin is contained; at the same time, the cured substances of the aromatic epoxy resin are easily crosslinked, making it difficult to achieve sufficient thermoplasticity.
A combination of an active hydrogen compound containing a pKa of 10 or less or an active hydrogen compound having a pKa of 10 or more and a cationic catalyst is used as a curing agent to improve the curing reactivity of the alicyclic epoxy resin, and a cured product having thermoplasticity is obtained by linear polymerization.
It realizes that even if a large amount of alicyclic epoxy resin can be included, the curing reaction can be carried out quickly, the curing time is shortened, and the curing substances are given good thermoplasticity and operability, and is suitable for a variety of industrial applications.
Smart Images

Figure CN119768447A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a curable composition, a cured product and a method for producing the cured product. Background Art
[0002] Epoxy resins are used in various electrical and electronic components. Among them, alicyclic epoxy resins are used in optical applications such as packaging materials for optical semiconductor elements and organic electroluminescent elements, and surface protection films, because of their low viscosity and high transparency and weather resistance of cured products.
[0003] On the other hand, alicyclic epoxy resins have significantly lower reactivity than general-purpose epoxy resins such as bisphenol epoxy resins. Therefore, the curing reaction cannot proceed in active hydrogen compounds such as amines or the curing takes a long time. Therefore, studies have been conducted to facilitate the curing reaction of alicyclic epoxy resins by using anhydride curing agents or improving the structure of epoxy resins (first study).
[0004] For example, Patent Document 1 discloses a curable composition comprising an alicyclic epoxy resin having a specific structure and an active hydrogen compound. An aliphatic amine curing agent is used as the active hydrogen compound. According to this document, by using an alicyclic epoxy resin having a specific structure, even an active hydrogen compound can be cured.
[0005] Patent Document 2 discloses a curable composition comprising an alicyclic epoxy resin, a polyfunctional thiol, a curing agent, and a curing accelerator. An aliphatic thiol is used as the polyfunctional thiol, an acid anhydride is used as the curing agent, and a p-toluenesulfonate of DBU is used as the curing accelerator.
[0006] Patent Document 3 discloses a curable composition comprising diglycidyl hexahydrophthalate, an alicyclic epoxy resin, a polythiol-based curing agent, and a curing accelerator.
[0007] In addition, epoxy resin is a thermosetting resin that is cured by reacting with a curing agent. Most thermosetting resins are usually in a liquid state before curing. Therefore, thermosetting resins have the following advantages: high adhesion to the adherend, easy to improve the bonding force; because it is in a liquid state and can ensure fluidity, the amount of filler added can be increased compared to thermoplastic resins; high dispersion of fillers can be achieved, etc.
[0008] Furthermore, thermoplastic resins can be recycled by melting them again. On the other hand, thermosetting resins do not melt once they are cured, and therefore cannot be recycled. That is, it is difficult to peel off the cured thermosetting resin after it is bonded to the adherend. Therefore, studies have been conducted to impart thermoplasticity to cured thermosetting resins such as epoxy resins (second study).
[0009] For example, Patent Document 4 discloses a composition comprising a difunctional aromatic epoxy resin (A), a difunctional phenol compound (B) and reinforcing fibers. Patent Document 5 discloses an adhesive comprising a difunctional aromatic epoxy resin, a difunctional curing agent and a curing catalyst. Patent Document 6 discloses an epoxy resin composition comprising a difunctional aromatic epoxy resin and at least one of a difunctional amine compound, a phenol compound and a thiol compound. By curing these compositions, a thermoplastic resin can be obtained in which a difunctional aromatic epoxy resin and a difunctional curing agent are polymerized in a linear state.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2021-55001
[0013] Patent Document 2: Japanese Patent Application Publication No. 2010-53199
[0014] Patent Document 3: Japanese Patent Application Publication No. 2007-109915
[0015] Patent Document 4: Japanese Patent Application Publication No. 2006-321897
[0016] Patent Document 5: Japanese Patent Application Publication No. 2019-194322
[0017] Patent Document 6: Japanese Patent Application Publication No. 2001-348419 Summary of the invention
[0018] Problem that the invention aims to solve
[0019] However, regarding the first study (curing reactivity of alicyclic epoxy resins), it is necessary to use alicyclic epoxy resins having a specific structure in Patent Document 1. It is desired that various alicyclic epoxy resins can be used without being limited to such a specific structure.
[0020] In addition, since the curable composition of Patent Document 2 contains a large amount of anhydride curing agent, although the curing reaction proceeds, it takes a long time to obtain a cured product. In addition, since the curable composition of Patent Document 3 contains a large amount of aromatic epoxy resin, the curing reaction is relatively easy to proceed, but when a large amount of alicyclic epoxy resin is contained, it takes a long time to obtain a cured product.
[0021] Therefore, it is desired that even if a large amount of alicyclic epoxy resin is contained, the curing reaction can be easily advanced and the time until a cured product is obtained can be shortened.
[0022] In addition, regarding the second study (imparting thermoplasticity to epoxy resin), since the epoxy resin contained in the compositions disclosed in Patent Documents 4 to 6 is an aromatic epoxy resin, when the composition is cured, not only the aromatic epoxy resin and the curing agent are likely to react, but also the aromatic epoxy resins are likely to react with each other. Therefore, a part of the aromatic epoxy resin is likely to crosslink, and the obtained cured product is unlikely to become a highly linearly polymerized polymer and does not have sufficient thermoplasticity.
[0023] In addition, to make the bifunctional compound react with each other, it is necessary to coordinate the resin and the curing agent in equivalent. Therefore, when the curing agent is solid, there is a problem of easy thickening. Especially in the aromatic epoxy resin with high viscosity, the viscosity significantly increases, so it is easy to lose the unique liquid property of thermosetting resin. And then, in the aromatic epoxy resin with high viscosity, not only the impregnation property to the adherend and the filler is low, but also there is a problem of being difficult to increase the content of the filler in order to suppress the increase of viscosity. In addition, when using an aromatic epoxy resin, if primary amines are used as a bifunctional curing agent, then due to three-dimensional crosslinking, it is impossible to obtain a polymer polymerized in a linear shape.
[0024] If the cured product has sufficient thermoplasticity, it can be remelted and thus can be recycled or self-repaired. For example, if the cured product bonded to the adherend can be softened or melted by heating, the cured product can be peeled off from the adherend, which can provide easy disassembly.
[0025] In addition, if the composition before curing is in a liquid state, shear kneading such as three-roll dispersion can be performed, so that high dispersion of the filler can be achieved. For example, if the composition containing the filler can be dispersed by shear kneading, and the cured product can be melted after curing, the filler that is difficult to disperse in the extruder for the thermoplastic resin can be added in a state dispersed as a masterbatch. Therefore, it is further desired to have good operability like a thermosetting resin and to give a cured product with thermoplasticity.
[0026] The present invention has been made in view of the above circumstances, and its object is to provide a curable composition, a cured product, and a method for producing a cured product that exhibit good curing reactivity even when a large amount of alicyclic epoxy resin is contained. Preferably, the present invention further aims to provide a curable composition and a thermoplastic resin that have good workability as good as a thermosetting resin and can provide a cured product having thermoplastic properties.
[0027] Technical Solution
[0028] The present invention relates to the following curable composition, cured product, method for producing a cured product, and thermoplastic resin.
[0029] [1] A curable composition comprising an alicyclic epoxy resin (A) and an active hydrogen compound (B1) having a pKa of 10 or less.
[0030] [2] The curable composition according to [1], wherein the active hydrogen compound (B1) includes an aromatic thiol compound.
[0031] [3] The curable composition according to [1] or [2], wherein the alicyclic epoxy resin (A) is a difunctional alicyclic epoxy resin (A'), and the active hydrogen compound (B1) having a pKa of 10 or less is a difunctional active hydrogen compound (B1') having a pKa of 10 or less.
[0032] [4] A curable composition comprising an alicyclic epoxy resin (A), an active hydrogen compound (B2) having a pKa greater than 10, and a cationic catalyst (C1), wherein the content ratio of the active hydrogen compound (B2) relative to 100 parts by mass of the alicyclic epoxy resin (A) is 40 to 200 (mass ratio).
[0033] [5] The curable composition according to [4], wherein the active hydrogen compound (B2) includes an aliphatic thiol compound.
[0034] [6] A curable composition comprising a difunctional alicyclic epoxy resin (A'), a difunctional active hydrogen compound (B2') having a pKa of more than 10, and a cationic catalyst (C1).
[0035] [7] A curable composition comprising an alicyclic epoxy resin (A), an active hydrogen compound (B2) having a pKa of more than 10, and a catalyst (C2) that generates a cation by reaction with the active hydrogen compound (B2) or by light irradiation.
[0036] [8] The curable composition according to [7], wherein the active hydrogen compound (B2) includes an aliphatic thiol compound.
[0037] [9] The curable composition according to [7] or [8], wherein the catalyst (C2) is a catalyst that generates a cationic catalyst by reacting with the active hydrogen compound (B2), and the catalyst (C2) includes dicyandiamide.
[0038]
[10] The curable composition according to any one of [7] to [9], wherein the alicyclic epoxy resin (A) is a difunctional alicyclic epoxy resin (A'), and the active hydrogen compound (B2) having a pKa of more than 10 is a difunctional active hydrogen compound (B2') having a pKa of more than 10.
[0039]
[11] A cured product, which is a cured product of the curable composition according to any one of [1] to
[10] .
[0040]
[12] A method for producing a cured product, comprising: a step of reacting an active hydrogen compound (B2) with dicyandiamide under heating to obtain a composition containing guanidine; and a step of reacting the composition with an alicyclic epoxy resin (A) under heating to obtain a cured product of the curable composition containing the alicyclic epoxy resin (A).
[0041]
[13] A thermoplastic resin comprising a structural unit derived from a difunctional alicyclic epoxy resin (A') and a structural unit derived from a difunctional active hydrogen compound (B').
[0042] Beneficial Effects
[0043] According to the present invention, a curable composition, a cured product, and a method for producing a cured product that exhibit good curing reactivity even when a large amount of alicyclic epoxy resin is contained can be provided. Preferably, a curable composition and a thermoplastic resin that have good workability as good as a thermosetting resin and can provide a cured product having thermoplastic properties can be further provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A and Figure 1 B is a photograph showing the appearance of the cured product obtained from Composition 2-6 before and after heating.
[0045] Figure 2 A and Figure 2 B is a photograph showing the appearance of the cured product obtained from Composition 2-7 before and after heating.
[0046] Figure 3 A is a diagram showing the curing reaction mechanism of composition 2-6, Figure 3 B is a diagram showing a TOF-MS (Time of Flight Mass Spectrometry) spectrum of the cured product.
[0047] Figure 4 A is a photograph showing the results of SEM (Scanning Electron Microscope) observation of the surface of the sample piece of composition 2-6. Figure 4 B and Figure 4 C is a photograph showing the results of EDX (Energy Dispersive X-Ray Spectroscopy). DETAILED DESCRIPTION
[0048] As described above, alicyclic epoxy resins, especially bifunctional alicyclic epoxy resins having an epoxy group consisting of two adjacent carbon atoms and an oxygen atom constituting an alicyclic ring (hereinafter also referred to as "alicyclic epoxy group"), have lower curing reactivity than general-purpose epoxy resins such as bisphenol epoxy resins.
[0049] In order to improve the curing reactivity of such alicyclic epoxy resins with low curing reactivity, H + (cationic) is effective in activating alicyclic epoxy resins.
[0050] Furthermore, the present inventors have found that the alicyclic epoxy resin can be easily activated and the curing reactivity can be improved by the following curing agent:
[0051] 1) As a curing agent, it is easy to release H + active hydrogen compounds with a low pKa; or
[0052] 2) As a curing agent, and with a hard-to-release H + An active hydrogen compound (i.e. an active hydrogen compound with a high pKa) and a cationic catalyst (C1); or
[0053] 3) As a curing agent, an active hydrogen compound with a high pKa and a catalyst (C2) that generates a cation by reaction or light irradiation with the active hydrogen compound are used. In particular, it was found that by using a thiol compound as the active hydrogen compound, a cured product with a high refractive index can be obtained; further, it was found that by using an aliphatic thiol compound, a cured product with a high refractive index, flexibility and a high bending modulus can be obtained.
[0054] That is, the curable composition of one embodiment of the present invention contains an alicyclic epoxy resin (A) and a component for curing the resin, wherein the component for curing the resin is:
[0055] 1) an active hydrogen compound (B1) having a pKa of 10 or less; or
[0056] 2) a combination of an active hydrogen compound (B2) having a pKa greater than 10 and a cationic catalyst (C1); or
[0057] 3) A combination of an active hydrogen compound (B2) having a pKa exceeding 10 and a catalyst (C2) that generates cations by reaction or light irradiation.
[0058] Furthermore, the present inventors have found that in the above curing system, the difunctional alicyclic epoxy resin (A') is easily linearly polymerized with the difunctional active hydrogen compound (B').
[0059] That is, in the curing system using an acid anhydride, the epoxy group of the alicyclic epoxy resin reacts with the acid anhydride and then opens the ring to form an oxygen anion (-O - ), and therefore it is easy to react (not only with the acid anhydride) but also with other alicyclic epoxy resins to form three-dimensional crosslinking (see below).
[0060] [Chemical formula 1]
[0061]
[0062] [Chemical formula 2]
[0063]
[0064] In contrast, in the curing systems 1) to 3) above, after the epoxy groups of the alicyclic epoxy resin react with the active hydrogen compound, the cationic (H + ) and become -OH, so it does not react with other alicyclic epoxy resins, but only reacts with active hydrogen compounds (see below). That is, since the reaction does not proceed via oxygen anions, it is not easy for alicyclic epoxy resins to react with each other. Therefore, it is not necessary to perform three-dimensional crosslinking, but linear bonding in the order of alicyclic epoxy resin-active hydrogen compound-alicyclic epoxy resin... can be performed. In this way, a cured product with thermoplasticity can be obtained.
[0065] [Chemical formula 3]
[0066]
[0067] [Chemical formula 4]
[0068]
[0069] Therefore, the curable composition has good operability as good as that of a thermosetting resin and can provide a cured product with thermoplasticity. In addition, for such a cured product with thermoplasticity, for example, even if cracks appear, they will soften or melt by heating, showing self-repairing properties such as the crack disappearing. Therefore, for example, the cured product bonded to the adherend can be softened or melted by heating, so that it can be peeled off from the adherend and recycled.
[0070] Hereinafter, the configuration of the curable composition will be described in detail.
[0071] 1. Curable composition
[0072] The curable composition according to one embodiment of the present invention comprises an alicyclic epoxy resin (A), an active hydrogen compound (B), and optionally a curing catalyst (C).
[0073] 1-1. Cycloaliphatic epoxy resin (A)
[0074] The alicyclic epoxy resin (A) is a compound having two or more epoxy groups in one molecule, preferably a compound having an epoxy group consisting of two or more adjacent carbon atoms and oxygen atoms constituting an alicyclic ring (hereinafter also referred to as "alicyclic epoxy group"). Thus, the epoxy group consisting of carbon atoms and oxygen atoms constituting an alicyclic ring has low curing reactivity, so it is particularly effective to cure it by the active hydrogen compound (B) / curing catalyst (C) described in 1) to 3).
[0075] The number of epoxy groups contained in one molecule of the alicyclic epoxy resin (A) is not particularly limited, but is preferably 2 or more, and more preferably 2 to 4. That is, the alicyclic epoxy resin (A) may be a difunctional alicyclic epoxy resin (A') having two epoxy groups in one molecule, or may be a trifunctional or higher alicyclic epoxy resin having three or more epoxy groups in one molecule.
[0076] The alicyclic epoxy group in the compound having an alicyclic epoxy group includes an epoxycyclohexyl group, an epoxycyclopentyl group, etc. Examples of the compound having an alicyclic epoxy group include a compound represented by the following formula (i).
[0077] [Chemical formula 5]
[0078]
[0079] In the above formula (i), X represents a single bond or a linking group. Examples of the linking group include: a divalent hydrocarbon group, an epoxidized alkenylene group (hereinafter also referred to as "epoxidized alkenylene group"), a carbonyl group, an ether bond, an ester bond, a siloxane bond, a carbonate group, an amide group, and a group formed by connecting a plurality of these. It should be noted that the epoxycyclohexane group in formula (i) is optionally bonded with a substituent (e.g., an alkyl group, etc.).
[0080] Examples of the divalent hydrocarbon group include a linear or branched alkylene group having 1 to 18 carbon atoms and a divalent alicyclic hydrocarbon group.
[0081] Examples of the linear or branched alkylene group having 1 to 18 carbon atoms include a methylene group, a methylmethylene group, a dimethylmethylene group, an ethylene group, a propylene group, and a trimethylene group.
[0082] Examples of the divalent alicyclic hydrocarbon group include cycloalkylene groups (including cycloalkylidene groups) such as 1,2-cyclopentylene, 1,3-cyclopentylene, cyclopentylidene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene, and cyclohexylene.
[0083] Examples of the alkenylene group in the epoxidized alkenylene group include straight-chain or branched alkenylene groups having 2 to 8 carbon atoms, such as vinylene, propenylene, 1-butenylene, 2-butenylene, butadienylene, pentenylene, hexenylene, heptenylene, and octenylene. The epoxidized alkenylene group is preferably an alkenylene group in which all carbon-carbon double bonds are epoxidized, and more preferably an alkenylene group having 2 to 4 carbon atoms in which all carbon-carbon double bonds are epoxidized.
[0084] Examples of the compound represented by formula (i) include (3,4,3',4'-diepoxy)bicyclohexane, bis(3,4-epoxycyclohexylmethyl)ether, 1,2-epoxy-1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, and compounds represented by the following formulas (i-1) to (i-9). In the following formulas (i-5) and (i-7), l and m each represent an integer from 1 to 30. In the following formula (i-5), R' is an alkylene group having 1 to 8 carbon atoms, and preferably a linear or branched alkylene group having 1 to 3 carbon atoms, such as a methylene group, an ethylene group, a propylene group, and an isopropylene group.
[0085] [Chemical formula 6]
[0086]
[0087] Examples of the compound having an alicyclic epoxy group include, in addition to the compound represented by the above formula (i), the following compounds.
[0088] [Chemical formula 7]
[0089]
[0090] Examples of compounds having an alicyclic epoxy group include, in addition to the compound represented by formula (i), compounds having three or more alicyclic epoxy groups in the molecule represented by the following formulas (ii-1) to (ii-3), and compounds having one alicyclic epoxy group in the molecule represented by the following formulas (iii-1) to (iii-3). In the following formulas (ii-1) and (ii-2), n1 to n6 represent integers of 1 to 30, respectively.
[0091] [Chemical formula 8]
[0092]
[0093] [Chemical formula 9]
[0094]
[0095] The epoxy equivalent of the alicyclic epoxy resin (A) is not particularly limited. For example, if it is for the purpose of increasing the refractive index, in order to increase the content of sulfur-containing active hydrogen compounds such as thiol compounds, the epoxy equivalent is preferably moderately low. Similarly, if it is for the purpose of increasing the bending modulus, in order to increase the content of polyfunctional active hydrogen compounds, the epoxy equivalent is preferably moderately low. From these viewpoints, the epoxy equivalent of the alicyclic epoxy resin (A) is preferably 70 to 200 g / eq, and more preferably 80 to 140 g / eq. The epoxy equivalent can be measured according to JIS K 7236.
[0096] The content of the alicyclic epoxy resin (A) also depends on the purpose, the presence or absence of fillers, etc., and can be, for example, 1 to 70 parts by mass relative to 100 parts by mass of the non-volatile components of the curable composition. If the content of the alicyclic epoxy resin (A) is within the above range, it is easy to obtain a curable composition with a lower viscosity, and it is easy to obtain a cured product with higher transparency and weather resistance. It should be noted that the non-volatile component refers to a component that does not volatilize at room temperature, specifically, it refers to a component other than a solvent.
[0097] 1-2. Active hydrogen compound (B) / curing catalyst (C)
[0098] The active hydrogen compound (B) is a compound containing a functional group having active hydrogen. Examples of functional groups having active hydrogen include phenolic hydroxyl groups, thiol groups, amino groups, etc. The number of functional groups having active hydrogen contained in one molecule of the active hydrogen compound (B) may be 2 or more. That is, the active hydrogen compound (B) may be a difunctional active hydrogen compound (B') having 2 functional groups having active hydrogen in one molecule, or may be a trifunctional or higher active hydrogen compound having 3 or more functional groups having active hydrogen.
[0099] Furthermore, as described above, the curable composition comprises, as a component for curing the alicyclic epoxy resin (A), 1) an active hydrogen compound (B1) having a pKa of 10 or less; or 2) an active hydrogen compound (B2) having a pKa of more than 10 and a cationic catalyst (C1); or 3) an active hydrogen compound (B2) having a pKa of more than 10 and a catalyst (C2) that generates a cation by reaction or light irradiation.
[0100] About 1)
[0101] (Active hydrogen compound (B1))
[0102] The pKa of the active hydrogen compound (B1) in 1) is 10 or less, preferably 6 to 10. Such an active hydrogen compound with a low pKa can easily release H +, so it is easy to activate the alicyclic epoxy resin. Therefore, even in the absence of a catalyst, the alicyclic epoxy resin can be cured. The active hydrogen compound (B1) can be a difunctional active hydrogen compound (B1') or a trifunctional or higher active hydrogen compound.
[0103] In this application specification, pKa is the acid dissociation equilibrium constant, which is defined as pKa = -logKa, Ka = [H3O + ][B - ] / [BH](BH: organic acid, B - : conjugate base of an organic acid). It should be noted that, when one molecule of the curing agent contains two or more acidic groups, pKa refers to the first dissociation constant pKa1.
[0104] The acid dissociation constant (pKa) of an active hydrogen compound varies depending on the structure of the active hydrogen compound. That is, the pKa of a compound in which a functional group having active hydrogen is directly bonded to an aromatic group (aromatic ring) is lower than the pKa of a compound in which a functional group having active hydrogen is directly bonded to an aliphatic group. In addition, the pKa decreases in the order of thiol < alcohol < amine.
[0105] In addition, the acid dissociation constant (pKa) also varies depending on the type of solvent surrounding the active hydrogen compound. In this specification, in order to distinguish between the active hydrogen compound (B1) and the active hydrogen compound (B2), the pKa in water is used as an indicator. The pKa can be calculated from the concentration of the substance and the hydrogen ion concentration by, for example, measuring the hydrogen ion concentration in water using a pH meter. Alternatively, when the pKa value is known in the literature (e.g., pKa Data Compiled by R. Williams, https: / / organicchemistrydata.org / hansreich / resources / pka / pka_data / pka-compilation-williams.pdf), the pKa value is used. When the pKa value is not known in the literature, the active hydrogen compound can be described by a simplified structural formula, and the pKa value of the compound having two or more carbon atoms starting from the carbon atom bonded to the functional group having active hydrogen (equivalent to the compound having two or more carbon atoms starting from the carbon atom bonded to the functional group having active hydrogen) is used.
[0106] In the case of a water-insoluble active hydrogen compound, the pKa value can be estimated from the structure around the functional group that becomes active hydrogen. For example, the pKa value of 4,4'-thiobisbenzenethiol can be the pKa value of thiophenol.
[0107] Examples of the active hydrogen compound (B1) having a pKa of 10 or less include thiol compounds having a pKa of 10 or less and bisphenol compounds having a pKa of 10 or less. These curing agents may be compounds in which an active hydrogen functional group such as thiol or alcohol is directly bonded to a conjugated structure such as a benzene ring. The curing agent in which the conjugated structure is bonded to the active hydrogen functional group is likely to release hydrogen ions because the conjugated base state is stabilized.
[0108] Bisphenol compounds having a pKa of 10 or less are compounds having two phenolic hydroxyl groups in one molecule, and examples thereof include bisphenols such as 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)ethane (bisphenol AD), bis(hydroxyphenyl)methane (bisphenol F), bisphenol fluorene, and biscresol fluorene.
[0109] The thiol compound having a pKa of 10 or less may be any compound having two or more thiol groups in one molecule and having a pKa satisfying the above range, and is preferably a thiol compound containing an aromatic ring (aromatic thiol compound). The number of aromatic rings contained in one molecule of the aromatic thiol compound may be at least 1, preferably 1 to 3, and more preferably 1 to 2.
[0110] Examples of the aromatic thiol compounds include 1,2-dimercaptobenzene, 1,3-dimercaptobenzene, 1,4-dimercaptobenzene, 1,2-bis(mercaptomethyl)benzene, 1,3-bis(mercaptomethyl)benzene, 1,4-bis(mercaptomethyl)benzene, 1,3-bis(mercaptoethyl)benzene, 1,4-bis(mercaptoethyl)benzene, 1,2-bis(mercaptomethoxy)benzene, 1,3-bis(mercaptomethoxy)benzene, 1,4-bis(mercaptomethoxy)benzene, 1,2-bis(mercaptoethoxy)benzene, 1,3-bis(mercaptoethoxy)benzene, 1,4-bis(mercaptoethoxy)benzene, 2,2'-dimercaptobiphenyl, 4,4'-dimercaptobiphenyl, 4,4'-dimercapto bifunctional aromatic thiol compounds such as bibenzyl, 2,5-toluenedithiol, 3,4-toluenedithiol, 1,4-naphthalenedithiol, 1,5-naphthalenedithiol, 2,6-naphthalenedithiol, 2,7-naphthalenedithiol, 2,4-dimethylbenzene-1,3-dithiol, 4,5-dimethylbenzene-1,3-dithiol, 9,10-anthracene dimethylthiol, 1,3-bis(p-methoxyphenyl)propane-2,2-dithiol, 1,3-diphenylpropane-2,2-dithiol, phenylmethane-1,1-dithiol, and 2,4-bis(p-mercaptophenyl)pentane; 1,2,3-trimercaptobenzene, 1,2,4-trimercaptobenzene, 1,3,5-trimercaptobenzene, 1,2 ,3-Tris(mercaptomethyl)benzene, 1,2,4-tris(mercaptomethyl)benzene, 1,3,5-tris(mercaptomethyl)benzene, 1,2,3-tris(mercaptoethyl)benzene, 1,2,4-tris(mercaptoethyl)benzene, 1,3,5-tris(mercaptoethyl)benzene, 1,2,3-tris(mercaptomethoxy)benzene, 1,2,4-tris(mercaptomethoxy)benzene, 1,3,5-tris(mercaptomethoxy)benzene, 1,2,3-tris(mercaptoethoxy)benzene, 1,2,4-tris(mercaptoethoxy)benzene, 1,3,5-tris(mercaptoethoxy)benzene, 1,2,3,4-tetramercaptobenzene, 1,2,3,5-tetramercaptobenzene, 1,2,4,5-tetramercaptobenzene, 1, Aromatic thiol compounds having three or more functional groups, such as 2,3,4-tetrakis(mercaptomethyl)benzene, 1,2,3,5-tetrakis(mercaptomethyl)benzene, 1,2,4,5-tetrakis(mercaptomethyl)benzene, 1,2,3,4-tetrakis(mercaptoethyl)benzene, 1,2,3,5-tetrakis(mercaptoethyl)benzene, 1,2,4,5-tetrakis(mercaptoethyl)benzene, 1,2,3,4-tetrakis(mercaptoethyl)benzene, 1,2,3,5-tetrakis(mercaptomethoxy)benzene, 1,2,4,5-tetrakis(mercaptomethoxy)benzene, 1,2,3,4-tetrakis(mercaptoethoxy)benzene, 1,2,3,5-tetrakis(mercaptoethoxy)benzene, and 1,2,4,5-tetrakis(mercaptoethoxy)benzene.
[0111] The aromatic thiol compound may contain a sulfur atom in addition to the thiol group. Examples of such aromatic thiol compounds include:
[0112] 1,2-bis(mercaptomethylthio)benzene, 1,3-bis(mercaptomethylthio)benzene, 1,4-bis(mercaptomethylthio)benzene, 1,2-bis(mercaptoethylthio)benzene, 1,3-bis(mercaptoethylthio)benzene, 1,4-bis(mercaptoethylthio)benzene, 4,4'-thiobisbenzenethiol and other bifunctional aromatic thiol compounds; 1,2,3-tris(mercaptomethylthio)benzene, 1,2,4-tris(mercaptomethylthio)benzene, 1,3,5-tris(mercaptomethylthio)benzene, 1,2,3-tris(mercaptoethylthio)benzene, 1,2 ,4-tris(mercaptoethylthio)benzene, 1,3,5-tris(mercaptoethylthio)benzene, 1,2,3,4-tetrakis(mercaptomethylthio)benzene, 1,2,3,5-tetrakis(mercaptomethylthio)benzene, 1,2,4,5-tetrakis(mercaptomethylthio)benzene, 1,2,3,4-tetrakis(mercaptoethylthio)benzene, 1,2,3,5-tetrakis(mercaptoethylthio)benzene, 1,2,4,5-tetrakis(mercaptoethylthio)benzene, 1,3,5-triazine-2,4,6-trithiol (thiocyanuric acid) and other trifunctional or higher aromatic thiol compounds. These may be used alone or in combination of two or more.
[0113] The thiol equivalent of the thiol compound having a pKa of 10 or less is not particularly limited, and is, for example, 300 g / eq or less, preferably 150 g / eq or less. When the thiol equivalent is within this range, the curing reactivity of the curable composition and the refractive index of the cured product can be easily further improved.
[0114] As described above, the number of thiol groups (number of functional groups) contained in one molecule of the thiol compound having a pKa of 10 or less is 2 (difunctional) or 3 or more (trifunctional or more), preferably 2 to 10, more preferably 2 to 4, and more preferably 3. When the number of thiol groups is within this range, the curing reactivity of the curable composition and the refractive index of the cured product can be easily further improved.
[0115] The weight average molecular weight of the thiol compound having a pKa of 10 or less is not particularly limited, but is preferably 100 to 10000, and more preferably 100 to 1000. The weight average molecular weight can be measured by GPC in terms of polystyrene.
[0116] Among them, the active hydrogen compound (B1) having a pKa of 10 or less preferably includes a thiol compound having a pKa of 10 or less, and more preferably includes a thiol compound having a pKa of 7 or less.
[0117] The content of the active hydrogen compound (B1) having a pKa of 10 or less is preferably 15 to 400 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of the alicyclic epoxy resin (A)). If the content of the active hydrogen compound (B1) is 15 parts by mass or more, it is easier to activate the alicyclic epoxy resin and it is easy to obtain sufficient curing reactivity. If the content of the active hydrogen compound (B1) is 400 parts by mass or less, it is easy to suppress the viscosity increase of the curing composition, so it is less likely to impair operability. From the same point of view, the content of the active hydrogen compound (B1) is more preferably 30 to 200 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of the alicyclic epoxy resin (A)).
[0118] About 2)
[0119] In the case of 2) above, as components for curing the alicyclic epoxy resin, an active hydrogen compound (B2) having a pKa exceeding 10 and a cationic catalyst (C1) are contained.
[0120] (Active hydrogen compound (B2))
[0121] The pKa of the active hydrogen compound (B2) in 2) is higher than 10, preferably 10 to 14. Since an active hydrogen compound having such a high pKa is difficult to release H + Therefore, it is difficult to activate the alicyclic epoxy resin when used alone. Therefore, H + The cationic catalyst (C1) can cure the alicyclic epoxy resin. The active hydrogen compound (B2) can be a difunctional active hydrogen compound (B2') or a trifunctional or higher active hydrogen compound.
[0122] The active hydrogen compound (B2) having a pKa of more than 10 preferably includes an amine compound having a pKa of more than 10 or a thiol compound having a pKa of more than 10.
[0123] The amine compound having a pKa exceeding 10 may be any compound having two or more amino groups in one molecule and having a pKa satisfying the above range, preferably 11 or more, more preferably 15 or more, and preferably includes an amine compound containing an aromatic ring (aromatic amine compound).
[0124] Examples of aromatic amine compounds include 4,4'-diaminodiphenyl sulfide (manufactured by Seika Co., Ltd., ASD) and 4,4'-diaminodiphenyl sulfone (manufactured by Seika Co., Ltd., Seika cure S). In the present invention, primary amines may also be used. The main reasons for this are believed to be that the primary amines become secondary amines after reaction, thereby changing the pKa; and the steric hindrance of the epoxy group of the alicyclic epoxy resin is greater than that of the aromatic epoxy resin.
[0125] The thiol compound having a pKa exceeding 10 may be any compound having two or more thiol groups in one molecule and having a pKa satisfying the above range, and is preferably a thiol compound not containing an aromatic ring (aliphatic thiol compound). The aliphatic thiol compound may be an aliphatic thiol compound having an ester bond in the molecule or an aliphatic thiol compound not having an ester bond in the molecule.
[0126] Examples of aliphatic thiol compounds having an ester bond in the molecule include 1,4-bis(mercaptobutyryloxy)butane (manufactured by Showa Denko K.K., Karenz difunctional aliphatic thiol compounds such as MT (registered trademark) BD1); trimethylolpropane tris (3-mercaptopropionate) (manufactured by SC Organic Chemical Co., Ltd., TMMP), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate (manufactured by SC Organic Chemical Co., Ltd., TEMPIC), pentaerythritol tetrakis (3-mercaptopropionate) (manufactured by SC Organic Chemical Co., Ltd., PEMP), tetraethylene glycol bis (3-mercaptopropionate) (manufactured by SC Organic Chemical Co., Ltd., EGMP-4), dipentaerythritol hexa (3-mercaptopropionate) (manufactured by SC Organic Chemical Co., Ltd., DPMP), pentaerythritol tetrakis (3-mercaptobutyrate) (manufactured by Showa Denko K.K., Karenz MT (registered trademark) PE1), 1,3,5-tris (3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6, (1H, 3H, 5H)-trione (manufactured by Showa Denko K.K., Karenz MT (registered trademark) NR1) and other trifunctional or higher aliphatic thiol compounds.
[0127] Examples of the aliphatic thiol-based compound having no ester bond in the molecule include compounds represented by the following formula (1) or (2).
[0128] [Chemical formula 10]
[0129]
[0130] In formula (1), R 1 and R 2 Each R is independently selected from the group consisting of a hydrogen atom or an alkyl group having 1 to 12 carbon atoms. 3 , R 4 , R 5 and R 6 Each is independently selected from the group consisting of mercaptomethyl, mercaptoethyl and mercaptopropyl.
[0131] Examples of the compound represented by formula (1) include 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril (manufactured by Shikoku Chemical Industry Co., Ltd., TS-G), (1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril (manufactured by Shikoku Chemical Industry Co., Ltd., C3 TS-G), 1,3,4,6-tetrakis(mercaptomethyl)glycoluril, 1,3,4,6-tetrakis(mercaptomethyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(2-mercaptoethyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(3-mercaptopropyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(mercaptomethyl)-3a,6a-dimethylglycoluril, 1,3,4,6-tetrakis(2-mercaptoethyl)-3a,6a-dimethylglycoluril, 1,3,4,6-tetrakis(3-mercaptopropyl)-3a,6a-dimethylglycoluril, etc. Among them, 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril and 1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril are particularly preferred.
[0132] [Chemical formula 11]
[0133] (R 8 ) m -A-(R 7 -SH) n (2)
[0134] In formula (2), A is a residue of a polyol having n+m hydroxyl groups.
[0135] R 7 Each of the groups is independently an alkylene group having 1 to 10 carbon atoms.
[0136] R 8 Each of the groups is independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.
[0137] m is an integer greater than or equal to 0.
[0138] n is an integer of 3 or more.
[0139] Examples of the compound represented by formula (2) include pentaerythritol tripropyl mercaptan (manufactured by SC Organic Chemicals Co., Ltd., Multhiol Y-3), pentaerythritol tetrapropyl mercaptan, etc. Among them, pentaerythritol tripropyl mercaptan is particularly preferred.
[0140] Furthermore, as the aliphatic thiol compound having no ester bond in the molecule, a trifunctional or higher functional polythiol compound having two or more thioether bonds in the molecule may be used. Examples of such thiol compounds include 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(2-mercaptoethylthio)propane, 1,2,3-tris(3-mercaptopropylthio)propane, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, tetrakis(mercaptomethylthiomethyl)methane, tetrakis(2-mercaptoethylthiomethyl)methane, and tetrakis(3-mercaptopropylthiomethyl)methane. , 1,1,3,3-tetrakis(mercaptomethylthio)propane, 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 1,1,5,5-tetrakis(mercaptomethylthio)-3-thiopentane, 1,1,6,6-tetrakis(mercaptomethylthio)-3,4-dithiohexane, 2,2-bis(mercaptomethylthio)ethanethiol, 3-mercaptomethylthio-1,7-dimercapto-2,6-dithioheptane, 3,6-bis(mercaptomethylthio)-1,9-dimercapto-2,5,8-trithiononane, 3-mercaptomethylthio-1,6-dimercapto-2,5-dithiohexane, 1,1,9,9-tetrakis(mercaptomethylthio)-5-(3,3-bis(mercaptomethylthio)-1-thiopropyl)3,7- Nonane disulfide, tris(2,2-bis(mercaptomethylthio)ethyl)methane, tris(4,4-bis(mercaptomethylthio)-2-thiobutyl)methane, tetrakis(2,2-bis(mercaptomethylthio)ethyl)methane, tetrakis(4,4-bis(mercaptomethylthio)-2-thiobutyl)methane, 3,5,9,11-tetrakis(mercaptomethylthio)-1,13-dimercapto-2,6,8,12-tetrathiotridecane, 3,5,9,11,15,17-hexa(mercaptomethylthio)-1,19-dimercapto-2,6,8,12,14,18-hexathiononadecane, 9-(2,2-bis(mercaptomethylthio)ethyl)-3,5,13,15-tetrakis(mercaptomethylthio)-1,17 -dimercapto-2,6,8,10,12,16-hexathioheptadecane, 3,4,8,9-tetrakis(mercaptomethylthio)-1,11-dimercapto-2,5,7,10-tetrathioundecane, 3,4,8,9,13,14-hexa(mercaptomethylthio)-1,16-dimercapto-2,5,7,10,12,15-hexathiohexadecane, 8-[bis(mercaptomethylthio)methyl]-3,4,12,13-tetrakis(mercaptomethylthio)-1,15-dimercapto-2,5,7,9,11,14-hexathiopentadecane, 4,6-bis[3,5-bis(mercaptomethylthio)-7-mercapto-2,6-dithioheptylthio]-1,3-dithiane, 4-[3,5-bis(mercaptomethylthio)-7-mercapto-2,6-dithioheptylthio]-6-mercaptomethylthio-1,3-dithiane, 1,1-bis[4-(6-mercaptomethylthio)-1,3-dithianylthio]-1,3-bis(mercaptomethylthio)propane, 1-[4-(6-mercaptomethylthio)-1,3-dithianylthio]-3-[2,2-bis(mercaptomethylthio)ethyl]-7,9-bis(mercaptomethylthio)-2,4,6,10-tetrathiaundecane, 3-[2-(1,3-dithiocyclobutyl)]methyl-7,9-bis(mercaptomethylthio)-1,11-dimercapto-2,4,6,10-tetrathiaundecane, 9-[2-(1,3-dithiocyclobutyl)]methyl-3,5, acyclic polythiol compounds such as 13,15-tetrakis(mercaptomethylthio)-1,17-dimercapto-2,6,8,10,12,16-hexathioheptadecane, 3-[2-(1,3-dithiocyclobutyl)]methyl-7,9,13,15-tetrakis(mercaptomethylthio)-1,17-dimercapto-2,4,6,10,12,16-hexathioheptadecane; 4,6-bis[4-(6-mercaptomethylthio)-1,3-dithianylthio]-6-[4-(6-mercaptomethylthio)-1,3-dithianylthio]-1,3-dithiane, 4-[3,4,8,9-tetrakis(mercaptomethylthio)-11-mercapto-2,5,7,10-tetrathioundecyl]-5-mercaptomethylthio-1, 3-dithiocyclopentane, 4,5-bis[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]-1,3-dithiocyclopentane, 4-[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]-5-mercaptomethylthio-1,3-dithiocyclopentane, 4-[3-bis(mercaptomethylthio) 2-{bis[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]methyl}-1,3-dithiocyclobutane, 2-[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]methyl}-1,3-dithiocyclobutane, Polythiol compounds having a cyclic structure such as 2-[5-dithiohexylthio]mercaptomethylthiomethyl-1,3-dithiocyclobutane, 2-[3,4,8,9-tetrakis(mercaptomethylthio)-11-mercapto-2,5,7,10-tetrathioundecylthiol]mercaptomethylthiomethyl-1,3-dithiocyclobutane, 2-[3-bis(mercaptomethylthio)methyl-5,6-bis(mercaptomethylthio)-8-mercapto-2,4,7-trithiooctyl]mercaptomethylthiomethyl-1,3-dithiocyclobutane, and 4-{1-[2-(1,3-dithiocyclobutyl)]-3-mercapto-2-thiopropylthio}-5-[1,2-bis(mercaptomethylthio)-4-mercapto-3-thiobutylthio]-1,3-dithiocyclopentane.
[0141] The thiol equivalent of the thiol compound having a pKa of more than 10 is not particularly limited, and is, for example, 90 to 160 g / eq, preferably 90 to 140 g / eq. When the thiol equivalent is within this range, the curing reactivity of the curable composition is good. It is easy to further improve the curing reactivity of the curable composition, and it is also easy to further improve the refractive index, bending modulus, etc. of the cured product.
[0142] The number of thiol groups (functional group number) contained in one molecule of the thiol compound having a pKa exceeding 10 is, as described above, 2 (difunctional) or 3 (trifunctional) or more, preferably 2 to 4, more preferably 3 to 4, and even more preferably 4. When the number of thiol groups is above the lower limit, it is easy to further improve the curing reactivity of the curable composition, and it is also easy to further improve the refractive index, bending modulus, etc. of the cured product. In addition, when the number of thiol groups is 4 or less, the number of thiol groups remaining without reaction can be further reduced, and the reduction in physical properties can be suppressed.
[0143] The weight average molecular weight of the thiol compound having a pKa exceeding 10 is not particularly limited, but is preferably 100 to 10000, and more preferably 100 to 1000. The weight average molecular weight can be measured by the same method as described above.
[0144] The content of the active hydrogen compound (B2) having a pKa exceeding 10 is 40 to 200 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of alicyclic epoxy resin). If the content of the above-mentioned curing agent (B2) is 40 parts by mass or more, it is easier to activate the alicyclic epoxy resin and it is easier to improve the curing reactivity. If the content of the active hydrogen compound (B2) is 200 parts by mass or less, the viscosity increase of the cured composition can be further suppressed, and therefore the operability is less likely to be impaired. From the same point of view, the content of the above-mentioned curing agent (B2) is more preferably 50 to 150 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of alicyclic epoxy resin).
[0145] (Cationic Catalyst (C1))
[0146] Cationic catalyst (C1) is a catalyst that promotes H +The released compound is a compound that does not promote the self-polymerization of the epoxy resin monomer but promotes the reaction of the epoxy resin with the active hydrogen compound. The so-called non-promotion of self-polymerization can be confirmed by the fact that the mixture consisting only of the epoxy resin and the catalyst does not generate heat (curing) due to heat. In the self-polymerization reaction, for one epoxy group, two epoxy groups react, that is, for an alicyclic epoxy resin having two epoxy groups, each molecule reacts with four epoxy groups, so the degree of crosslinking increases and the toughness is easily reduced. In contrast, the cationic catalyst (C1) does not undergo such a self-polymerization reaction, and plays a role in promoting the activation of the epoxy group and the activation of the active hydrogen compound. By directly adding a cationic catalyst (C1) that becomes a cationic, the reaction can be carried out rapidly. Therefore, in an environment where heating cannot be performed, such as in cold areas, and in the case where the heating / light irradiation energy required to generate cationic species like the catalyst (C2) is desired to be suppressed, it can also be used as a catalyst for a two-liquid curable composition.
[0147] Activation of epoxy groups refers to interaction with the oxygen of epoxy groups, making the carbon of epoxy groups more susceptible to nucleophilic attack. As compounds that can interact with the oxygen of epoxy groups, positively charged compounds can be cited. As a reaction mechanism, the oxygen atom of the epoxy group interacts with the positively charged catalyst, making the carbon atom of the epoxy group carry a small amount of positive charge, thereby promoting the nucleophilic attack of the active hydrogen compound. Activation of active hydrogen compounds refers to the extraction of hydrogen from active hydrogen compounds.
[0148] Therefore, the cationic catalyst (C1) is a base used when curing the epoxy resin, and is preferably a compound that maintains a positive charge after abstracting hydrogen and has a steric structure capable of interacting with oxygen of an epoxy group.
[0149] Such a cationic catalyst (C1) is preferably an amine. Examples of the amine include ammonium salts, amines having an amidine structure, and amines having a guanidine structure.
[0150] Examples of the ammonium salt include triethylmethylammonium 2-ethylhexane salt (product name: U-CAT 18X, manufactured by SAN-APRO Co., Ltd.).
[0151] Examples of the amines having an amidine structure include diazabicycloundecene (DBU) and diazabicyclononene (DBN), and examples of salts of the amines include 2-ethylhexanoate of DBU (product name: SA1, manufactured by SAN-APRO).
[0152] Examples of amines having a guanidine structure (including polyguanidine) include tetramethylguanidine, and examples of salts include 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidine n-butyltriphenylborate (product name: WPGK-300 (Fuji Film Wako)).
[0153] Among them, amines having an amidine structure or salts thereof, and amines having a guanidine structure or salts thereof are preferred, and amines having a guanidine structure or salts thereof are more preferred.
[0154] The content of the cationic catalyst (C1) is preferably 1 to 10 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of alicyclic epoxy resin). If the content of the cationic catalyst (C1) is 1 part by mass or more, it is easier to activate the alicyclic epoxy resin and it is easy to obtain sufficient curing reactivity. If the content of the cationic catalyst (C1) is 10 parts by mass or less, after adding the catalyst, the time that can be used without curing (referred to as the usable time) can be further extended. In addition, the reduction in physical properties such as the glass transition temperature and elastic modulus caused by excessive residue of the catalyst in the cured product can be further suppressed. From the same point of view, the content of the cationic catalyst (C1) is more preferably 1 to 5 parts by mass relative to 100 parts by mass of the total amount of the resin containing an epoxy group (preferably the total amount of alicyclic epoxy resin).
[0155] About 3)
[0156] In the case of 3) above, as components for curing the alicyclic epoxy resin, an active hydrogen compound (B2) having a pKa exceeding 10 and a catalyst (C2) that generates cations by reaction or light irradiation are contained.
[0157] As mentioned above, active hydrogen compounds with high pKa are difficult to release H + Therefore, it is difficult to activate the alicyclic epoxy resin when used alone. Therefore, by further combining, H + The catalyst (C2) can improve the curing reactivity of the alicyclic epoxy resin. In addition, since the curing timing can be adjusted by the timing of the reaction and light irradiation, it is easy to take into account the storage stability. In addition, the curable composition containing the catalyst (C2) has fluidity even when stored at 40°C / 24 hours, for example, and has excellent storage stability. Therefore, the catalyst (C2) is particularly suitable as a catalyst for a one-component curable composition.
[0158] (Active hydrogen compound with pKa exceeding 10 (B2))
[0159] The active hydrogen compound (B2) having a pKa of more than 10 can be the same as those described above, and can be selected according to the type of catalyst (C2). For example, when the catalyst (C2) is dicyandiamide, the active hydrogen compound (B2) is preferably an active hydrogen compound that reacts with dicyandiamide to form guanidine (reaction accelerator).
[0160] When the active hydrogen compound (B2) is a thiol compound, dicyandiamide reacts as follows by heating to produce guanidine.
[0161] [Chemical formula 12]
[0162]
[0163] The generated guanidine further reacts with a thiol compound to form a guanidinium ion, thereby promoting the ring-opening of the alicyclic epoxy resin (see below).
[0164] [Chemical formula 13]
[0165]
[0166] The compound that reacts with dicyandiamide to form guanidine is preferably an aliphatic thiol compound, more preferably a tetrafunctional or higher-functional aliphatic thiol compound, and further preferably 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril and 1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril.
[0167] The content of the active hydrogen compound (B2) having a pKa exceeding 10 may be the same as in the case of 2) above. (Catalyst (C2) that generates cations by reaction or light irradiation)
[0168] The catalyst (C2) that generates cations by reaction or light irradiation is a catalyst that generates cations by reaction with the active hydrogen compound (B2) or light irradiation.
[0169] As for the catalyst that generates a cation by reaction, after activating the active hydrogen compound (B2), it has the same function as the cationic catalyst (C1) except that it contributes to the activation of the epoxy group by carrying a positive charge. Examples of such catalysts include dicyandiamide and the like. By controlling the reaction with the active hydrogen compound (B2), the curing start can be controlled, so it is preferred.
[0170] Examples of the catalyst that generates cations by light irradiation include photobase generators, and examples of the photobase generator include carboxylate salts, salts containing borate anions, and quaternary ammonium salts.
[0171] When a carboxylate or a salt containing a borate anion is used, a strong base such as amidine, guanidine, or phosphazene base can be generated from a weak base such as an aliphatic amine compound. Therefore, the reaction with the alicyclic epoxy resin easily proceeds in a chain reaction, and the curing reactivity is easily improved.
[0172] When a quaternary ammonium salt is used, it is preferred to contain imidazole or amidine as the base-reactive substance from the viewpoint of improving curing reactivity.
[0173] Among them, from the viewpoint of easily generating a strong base and easily improving the curing reactivity, preferred are (8E)-8-ethylidene-4-methoxy-5,6,7,8-tetrahydronaphthalene-1-carboxylic acid 1,8-diazabicyclo[5,4,0]undec-7-ene salt, 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidinium 2-(3-benzoylphenyl)propionate salt, 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidinium n-butyltriphenylborate, and (2-(9-oxobenzofluoren-2-yl)propionic acid-1,5,7-triazabicyclo[4,4,0]dec-5-ene salt).
[0174] The content of the catalyst (C2) is 0.5 to 10 parts by mass relative to 100 parts by mass of the total amount of the resin containing the epoxy group (preferably the total amount of the alicyclic epoxy resin). If the content of the catalyst (C2) is 0.5 parts by mass or more, it is easier to activate the alicyclic epoxy resin and it is easy to obtain sufficient curing reactivity. If the content of the catalyst (C2) is 10 parts by mass or less, it is possible to further suppress the reduction in physical properties such as the glass transition temperature and elastic modulus caused by excessive residue of the catalyst in the cured product. From the same point of view, the content of the catalyst (C2) is more preferably 1 to 5 parts by mass relative to 100 parts by mass of the total amount of the resin containing the epoxy group (preferably the total amount of the alicyclic epoxy resin).
[0175] In addition, when a cationic catalyst (C2) is generated by reaction, the content of the catalyst (C2) is preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the active hydrogen compound (B2). When the content of the catalyst (C2) is within the above range, a sufficient amount of guanidine is easily generated by reaction with the active hydrogen compound (B2), and curing reactivity is easily further improved.
[0176] 1-3. Other ingredients
[0177] The curable composition may further contain other components according to the application. Examples of other components include other epoxy resins, sensitizers, antioxidants, surfactants, coupling agents, stabilizers, fillers, solvents, and the like.
[0178] Examples of other epoxy resins include aliphatic epoxy resins, aromatic epoxy resins, etc. When the curable composition further contains other epoxy resins, the content of the other epoxy resins is preferably less than that of the alicyclic epoxy resin from the viewpoint of suppressing a decrease in storage stability and bending modulus.
[0179] In addition, when using a catalyst (C2) that generates cations by light irradiation, a sensitizer can be further used. The sensitizer has the function of increasing the sensitivity of the curing reaction. The sensitizer can be any compound that can transfer stimulating energy such as heat and light to other substances, and a sensitizer containing a naphthalene structure, anthracene structure or thioxanthone structure can be used. From the viewpoint of increasing the activity of the catalyst (C2), the mass ratio of the sensitizer to the catalyst (C2) (sensitizer / catalyst (C2)) can be, for example, 0.1 to 0.5.
[0180] In addition, when a thiol compound is used as the active hydrogen compound (B), the pot life can be extended by using a stabilizer as a curing accelerator. Examples of the stabilizer include boric acid esters such as triethyl borate, triisopropyl borate, trimethyl borate, tri-n-propyl borate, and tri-n-butyl borate.
[0181] In addition, when the curable composition is used for coatings, etc., since the viscosity of the alicyclic epoxy resin (A) is low, it can be expected that it can be used without adding a solvent, but when a lower viscosity is required, a solvent may be further included. The content of the solvent is preferably 0 to 100% relative to the non-volatile component of the curable composition, more preferably 0 to 50%, and even more preferably 0 to 20%.
[0182] In addition, from the viewpoint of further shortening the curing time of the curable composition, the content of the acid anhydride curing agent is preferably small. Specifically, the content of the acid anhydride curing agent can be 40 parts by mass or less, preferably 20 parts by mass or less, and more preferably 10 parts by mass or less relative to 100 parts by mass of the curable composition.
[0183] In addition, in the above-mentioned embodiment, a curable composition comprising an alicyclic epoxy resin (A), an active hydrogen compound (B) and an arbitrary curing catalyst (C) is shown, but it is not limited to this. It can also be made into a two-liquid curable composition composed of a first liquid and a second liquid mixed during use.
[0184] For example, when a cationic catalyst (C1) is used, a two-component curable composition can be prepared by combining a first liquid containing an alicyclic epoxy resin (A) and a cationic catalyst (C1) with a second liquid containing a diactive hydrogen compound (B2). It should be noted that the alicyclic epoxy resin (A) only needs to be contained in at least one of the first liquid and the second liquid. From the perspective of easy mixing, the viscosity of the two-component curable composition is preferably close to that of the first liquid and the second liquid. That is, in order to adjust the viscosity of the first liquid and the second liquid, the alicyclic epoxy resin (A) can be contained in both the first liquid and the second liquid.
[0185] In addition, when a catalyst (C2) is used, a two-liquid curable composition can be prepared by combining a first liquid containing an alicyclic epoxy resin (A) with a second liquid containing an active hydrogen compound (B2) and a catalyst (C2). From the viewpoint of easy mixing, the viscosity of the two-liquid curable composition is preferably close to that of the first liquid and the second liquid. In the case where an alicyclic epoxy resin (A) is added to both the first liquid and the second liquid in order to adjust the viscosity of the first liquid and the second liquid, a two-liquid curable composition can also be prepared by combining a first liquid containing an alicyclic epoxy resin (A) and a catalyst (C2) with a second liquid containing an alicyclic epoxy resin (A) and an active hydrogen compound (B2).
[0186] It should be noted that in the curable composition of the above embodiment, both the (A) component and the (B) component can be combined with components having any number of functional groups, but from the viewpoint of having good curing reactivity and further imparting a thermoplastic resin to the cured product, it is preferred to combine a difunctional (A) component and a difunctional (B) component.
[0187] That is, the curable composition may include a difunctional alicyclic epoxy resin (A'), a difunctional active hydrogen compound (B') and an arbitrary curing catalyst (C). Furthermore, the curable composition as a component for curing the difunctional alicyclic epoxy resin (A') may:
[0188] 1) a difunctional active hydrogen compound (B1') having a pKa of 10 or less; or
[0189] 2) comprising a difunctional active hydrogen compound (B2') having a pKa greater than 10 and a cationic catalyst (C1); or
[0190] 3) A bifunctional active hydrogen compound (B2') having a pKa exceeding 10 and a catalyst (C2) that generates cations by reaction or light irradiation.
[0191] The difunctional alicyclic epoxy resin (A') is the above-mentioned difunctional alicyclic epoxy resin (A'). Examples of the difunctional alicyclic epoxy resin (A') include the compound represented by the above-mentioned formula (i).
[0192] The difunctional active hydrogen compound (B1′) is the above-mentioned difunctional active hydrogen compound (B1′). Examples of the difunctional active hydrogen compound (B1′) include the above-mentioned difunctional bisphenol compounds having a pKa of 10 or less and difunctional thiol compounds having a pKa of 10 or less.
[0193] The thiol equivalent of the bifunctional thiol compound having a pKa of 10 or less is not particularly limited, but is, for example, 2000 g / eq or less, preferably 60 to 250 g / eq. When the thiol equivalent is within this range, the curing reactivity of the curable composition and the refractive index of the cured product can be further improved.
[0194] The difunctional active hydrogen compound (B2') is the above-mentioned difunctional active hydrogen compound (B2'). Examples of the difunctional active hydrogen compound (B2') include the above-mentioned difunctional amine compounds having a pKa of more than 10 and difunctional thiol compounds having a pKa of more than 10.
[0195] The thiol equivalent of the bifunctional thiol compound having a pKa exceeding 10 is not particularly limited, and is, for example, 90 to 180 g / eq, and preferably 110 to 160 g / eq. When the thiol equivalent is within this range, the curing reactivity of the curable composition is good.
[0196] The cationic catalyst (C1) and the catalyst (C2) that generates cations by reaction or light irradiation are the same as the above-mentioned cationic catalyst (C1) and the catalyst (C2) that generates cations by reaction or light irradiation.
[0197] The specific examples and contents of the difunctional alicyclic epoxy resin (A'), the difunctional active hydrogen compound (B1'), the difunctional active hydrogen compound (B2'), the cationic catalyst (C1), and the catalyst (C2) that generates a cation by reaction or light irradiation may be the same as those in the above-mentioned embodiment. In addition, the mass ratio of the difunctional alicyclic epoxy resin (A') to the difunctional active hydrogen compound (B1') or the difunctional active hydrogen compound (B2') may be the same as the mass ratio of the above-mentioned alicyclic epoxy resin (A) to the active hydrogen compound (B1) or the active hydrogen compound (B2).
[0198] 2. Cured product
[0199] A cured product according to one embodiment of the present invention is a cured product of the above-mentioned curable composition.
[0200] (Refractive Index)
[0201] Although the cured product of alicyclic epoxy resin has good transparency, it has no aromatic ring and therefore tends to have a lower refractive index than the cured product of aromatic epoxy resin. In contrast, when the active hydrogen compound (B) of the curable composition includes a thiol compound, the cured product includes sulfur and thus has a high refractive index. A cured product having a high refractive index is suitable for optical applications, for example.
[0202] The refractive index of the cured product consisting only of resin at a wavelength of 589 nm (approximately the wavelength of the D line) is preferably 1.52 or more, more preferably 1.52 to 1.70, and even more preferably 1.56 to 1.66. Furthermore, inorganic particles may be added to increase the refractive index. The refractive index can be measured using an Abbe refractometer at a wavelength of 589 nm.
[0203] The refractive index of the cured product can be adjusted by the type, content, number of functional groups (thiol groups) of the thiol compound contained in the curable composition. For example, aromatic thiol compounds are more likely to increase the refractive index of the cured product than aliphatic thiol compounds. In addition, when the content of the thiol compound in the curing composition is high and the number of functional groups is high, the refractive index of the cured product tends to become high.
[0204] (Bending characteristics)
[0205] The solidified material of the curable composition of the existing anhydride curing agent or cationic curing agent is easy to become brittle due to having a high crosslinking density. In contrast, the above-mentioned curable composition, when containing a thiol compound as an active hydrogen compound (B), particularly an aliphatic thiol compound as a curing agent (refer to above-mentioned 2) and 3)), can give the solidified material flexibility, so it is easy to improve toughness. That is, the solidified material of the curable composition comprising a thiol compound has good flexibility, and shows a high bending elastic modulus equivalent to that of the case using anhydride curing agent. The reason is not clear, but it can be inferred as follows.
[0206] The first reason is that, in thiol compounds, since the reaction mechanism does not involve oxygen anions, alicyclic epoxy resins do not react with each other. Therefore, the soft structure derived from the thiol compound is easily incorporated into the molecular structure relatively uniformly.
[0207] As the second reason, since the curing reactivity of alicyclic epoxy resin and thiol-based compounds is high, the hydroxyl groups generated by ring-opening are also many. Therefore, by hydrogen bonding between the generated hydroxyl groups, high elastic modulus is shown relative to the initial stress. On the other hand, if stress above hydrogen bonding is applied, the hydrogen bond breaks and low elastic modulus is shown, so it is believed that high strain rate and yield point are shown.
[0208] Specifically, the cured product of the curable composition may have a yield point in a stress-strain curve of a bending test according to JIS K 7171. The flexural modulus of the cured product containing no filler measured by the bending test is preferably 2900 to 4000 N / mm. 2 , more preferably 3100 to 3600 N / mm 2 , more preferably 3200 to 3500 N / mm 2In addition, the bending strength of the cured product measured by the above bending test is preferably 100 to 180 N / mm 2 , more preferably 110 to 180 N / mm 2 , more preferably 130 to 170 N / mm 2 Furthermore, the strain rate of the cured product measured by the above-mentioned bending test is preferably 4 to 10%, more preferably 5 to 10%, and even more preferably 8 to 10%.
[0209] The bending test of the cured product can be performed in accordance with JIS K 7171.
[0210] That is, a cured product with a thickness of 3 mm was cut into a size of 80 mm × 10 mm as a test piece. Using the test piece, the support distance was set to 50 mm, the test speed was set to 1.5 mm / min, and the bending elastic modulus, bending strength, and bending strain (hereinafter referred to as strain rate) were measured by a three-point bending test according to the method of JIS K 7171. The yield point is the initial point where strain increases without stress increase during the test.
[0211] The flexural modulus, strain rate and flexural strength of the cured product can be adjusted by the type and number of functional groups of the thiol compound. For example, if the thiol compound has a ring structure or has a large number of functional groups, the flexural modulus of the cured product tends to increase.
[0212] The cured product of the curable composition comprising the active hydrogen compound (B2) described in 3) and dicyandiamide as a catalyst (C2) contains guanidine as a main product and thiocyanate as a by-product generated by the reaction with the active hydrogen compound (B2).
[0213] The content of guanidine in the cured product is, for example, 0.005 to 1 mass %, or preferably 0.01 to 0.2 mass %.
[0214] The guanidine content can be measured by ion chromatography. Specifically, the measurement can be performed according to the following steps.
[0215] 1) First, use a hammer to pre-crush the solidified material to a size that can be put into a grinder (if it cannot be crushed, crush it under refrigeration). Set the M22 blade on the IKA universal grinder M20, put the pre-crushed material in a water-cooled state, and crush it for 1 minute. Sieve the crushed solidified material with a 60-mesh sieve, and repeat until about 2g of fine powder is obtained.
[0216] 2) Then, add 5 times the amount of water of the obtained fine powder, heat at 120°C / 20 hours in a PCT pressure vessel, cool to room temperature, and filter using filter paper (5C). The obtained extract is weighed into a test tube, fixed to volume with water, dissolved or extracted with ultrasound for 10 minutes, and filtered with a membrane filter.
[0217] 3) The obtained solution was subjected to ion chromatography measurement. The measurement conditions were as follows.
[0218] (Measurement conditions)
[0219] Device: TOSOH IC-2010.
[0220] Chromatographic column: Shodex IC YS-50 (125×4.6 mm ID (inner diameter)).
[0221] Short chromatographic column: Shodex IC YS-G (10×4.6mm ID).
[0222] Suppressor: No suppressor.
[0223] Eluent: 4 mM CH3SO3H.
[0224] Eluent flow rate: 1.0 mL / min.
[0225] Column temperature: 40℃.
[0226] Injection volume: 30μl.
[0227] Detector: Conductivity detector (CD).
[0228] In addition, when the curable composition contains a difunctional alicyclic epoxy resin (A') and a difunctional active hydrogen compound (B'), the cured product has a structure in which the difunctional alicyclic epoxy resin (A') and the difunctional active hydrogen compound (B') are polymerized in a linear form, and thus has sufficient thermoplasticity. That is, the cured product is a thermoplastic resin containing a structural unit derived from the difunctional alicyclic epoxy resin (A') and a structural unit derived from the difunctional active hydrogen compound (B').
[0229] The mass ratio of the structural units derived from the difunctional alicyclic epoxy resin (A') to the structural units derived from the difunctional active hydrogen compound (B') (difunctional active hydrogen compound (B1') or difunctional active hydrogen compound (B2')) in the above-mentioned thermoplastic resin is the same as the mass ratio of the difunctional alicyclic epoxy resin (A') to the difunctional active hydrogen compound (B') (difunctional active hydrogen compound (B1') or difunctional active hydrogen compound (B2')) in the above-mentioned curable composition.
[0230] The total content of the structural unit derived from the difunctional alicyclic epoxy resin (A') and the structural unit derived from the difunctional active hydrogen compound (B') is 4% by mass or more, preferably 60% by mass or more, relative to the non-volatile components of all structural units constituting the thermoplastic resin. If the above total content is within the above range, it is easy to obtain higher thermoplasticity. In addition, when the active hydrogen compound (B') is a thiol compound, it is easy to further increase the refractive index of the thermoplastic resin.
[0231] The above-mentioned thermoplastics have self-healing properties.
[0232] That is, the thermoplastic resin has sufficient thermoplasticity because the difunctional alicyclic epoxy resin (A') and the difunctional active hydrogen compound (B') are highly linearly polymerized, and the molecules can easily move by heating, thereby showing self-healing properties at the physical level.
[0233] In addition, the thermoplastic resin is easy to form hydrogen bonds between molecules because the epoxy group of the alicyclic epoxy resin (A') has multiple hydroxyl groups generated by the reaction with the difunctional active hydrogen compound (B'). In addition, when the active hydrogen compound (B') contains an aromatic ring, π-π bonds are easy to form between molecules. Through these reversible bonds, self-healing properties at the chemical level are displayed.
[0234] It is considered that the above-mentioned thermoplastics exhibit self-healing properties due to these effects.
[0235] 3. Method for producing cured product
[0236] The cured product can be produced by heating the curable composition to cure it.
[0237] The heating temperature also depends on the type of active hydrogen compound (B), and when a thiol compound is used, for example, it may be 0 to 250° C., preferably 60 to 120° C., and more preferably 100 to 120° C. The heating time may be 0.02 to 3 hours, and preferably 0.1 to 1 hour.
[0238] When the curable composition contains the catalyst (C2) that generates a cation through reaction as described in 3), the alicyclic epoxy resin (A), the active hydrogen compound (B2) and the catalyst (C2) may be mixed simultaneously and then heated to cure; or the active hydrogen compound (B2) and the catalyst (C2) may be reacted first, and then the alicyclic epoxy resin (A) may be mixed and heated to cure.
[0239] For example, a cured product can also be obtained by the following steps: a step of reacting an active hydrogen compound (B2) with dicyandiamide under heating to obtain a composition containing guanidine; and a step of reacting the composition with an alicyclic epoxy resin (A) under heating to obtain a cured product. In this way, by reacting the active hydrogen compound (B2) with dicyandiamide before mixing with the alicyclic epoxy resin (A), the curing reaction can be started in a shorter time, and the curing reaction can be made to occur more easily.
[0240] The heating temperature when reacting the active hydrogen compound (B2) with dicyandiamide may be any temperature within the range of the reaction of the active hydrogen compound (B2) with dicyandiamide, for example, 60 to 120°C, more preferably 100 to 120°C. The reaction time may be any temperature within the range of generating a certain amount of guanidinium ions, for example, and it depends on the temperature, for example, 0.1 to 1 hour. After heating to a temperature at which dicyandiamide and thiol can react, the mixture may be cooled and solidified at a low temperature below room temperature, or it may be solidified in a short time by maintaining the temperature after heating or raising the temperature to the above-mentioned heating temperature range.
[0241] In addition, when the curable composition contains the catalyst (C2) that generates cations by light irradiation, the light irradiation conditions may be within a range that allows the photobase generator to generate a base. For example, the wavelength of the irradiated light is preferably 200 to 500 nm. In addition, the irradiation amount may be 10 to 10000 mJ / cm 2 After generating cations by light irradiation, the material may be cured at a low temperature below room temperature, or it may be cured in a short time by raising the temperature to the above-mentioned heating temperature range.
[0242] 4. Use of solidified materials
[0243] Since the above-mentioned cured product is made of a curable composition containing an alicyclic epoxy resin (A), it has good transparency and weather resistance. In particular, by using a thiol compound as an active hydrogen compound (B), a cured product having a high refractive index, moderate softness, bending elastic modulus, etc. can be obtained in addition to being able to be cured by light irradiation or low-temperature heating. Therefore, the cured product can be preferably used in optical applications such as packaging materials, adhesives, surface protective films, transparent display substrates, etc. for optical semiconductor elements and organic electroluminescent elements; and structural adhesive materials for manufacturing environments such as the automotive industry, which are difficult to heat the entire adherend and need to withstand damage such as collisions; protective films for touch panel sensors, coatings for protecting the surfaces of electronic devices, automobiles, etc. In particular, since the cured product has a high elastic modulus, the bonding position of the adherend can be maintained under weak external forces, and since the cured product has a yield point, it can be bent without breaking under strong external forces. Therefore, the cured product is suitable for structural adhesives in the automotive industry, etc.
[0244] Example
[0245] Hereinafter, the present invention will be further described with reference to Examples and Comparative Examples, but the technical scope of the present invention is not limited thereto.
[0246] 1. Preparation of Materials
[0247] 1-1. Epoxy resin
[0248] <Alicyclic Epoxy Resin (A)>
[0249] A-1: CELLOXIDE 2021P (manufactured by Daicel Corporation, difunctional, epoxy equivalent 130 g / eq).
[0250] [Chemical formula 14]
[0251]
[0252] A-2: CELLOXIDE 8010 (manufactured by Daicel Corporation, difunctional, epoxy equivalent 100 g / eq).
[0253] [Chemical formula 15]
[0254]
[0255] A-3: CELLOXIDE 2081 (manufactured by Daicel Corporation, difunctional, epoxy equivalent 200 g / eq) A-4: THI-DE (manufactured by ENEOS Corporation, difunctional, epoxy equivalent 80 g / eq).
[0256] [Chemical formula 16]
[0257]
[0258] A-5: X-40-2669 (manufactured by Shin-Etsu Chemical Co., Ltd., difunctional, epoxy equivalent 200 g / eq).
[0259] [Chemical formula 17]
[0260]
[0261] A-6: KR-470 (manufactured by Shin-Etsu Chemical Co., Ltd., tetrafunctional, epoxy equivalent 200 g / eq).
[0262] [Chemical formula 18]
[0263]
[0264] <Aromatic epoxy resin>
[0265] 835LV (manufactured by DIC Corporation, Bis A / F type epoxy resin, epoxy equivalent 165 g / eq).
[0266] JER604 (manufactured by Mitsubishi Chemical Corporation, tetrafunctional, epoxy equivalent 120 g / eq).
[0267] JER630 (manufactured by Mitsubishi Chemical Corporation, trifunctional, epoxy equivalent 98 g / eq).
[0268] 850S (manufactured by DIC Corporation, difunctional, epoxy equivalent 189 g / eq).
[0269] 1-2. Curing agent
[0270] <Active hydrogen compound with pKa of 10 or less (B1)>
[0271] B1-1: 1,3,5-triazine-2,4,6-trithiol (thiocyanuric acid) (manufactured by Tokyo Chemical Industry Co., Ltd., aromatic thiol (trifunctional), thiol equivalent 59.1 g / eq, pKa 4 - 6.5).
[0272] B1-2: 4,4'-thiobisbenzenethiol (manufactured by Fujifilm Wako Pure Chemical Corporation, aromatic thiol (difunctional), thiol equivalent 126.2 g / eq, C6H5SH: pKa 6.52 - 8.2).
[0273] B1-3: Bisphenol A (manufactured by Mitsui Chemicals, Inc., phenol (difunctional), hydroxyl equivalent 114 g / eq, literature value: pKa 9.6).
[0274] <Active hydrogen compound with pKa exceeding 10 (B2)>
[0275] B2-1: TS-G (manufactured by Shikoku Chemicals Co., Ltd., aliphatic thiol (tetrafunctional), thiol equivalent 96 g / eq, CH3CH2SH: pKa 10.5).
[0276] [Chemical formula 19]
[0277]
[0278] B2-2: PEMP (manufactured by SC Organic Chemical Co., Ltd., aliphatic thiol (tetrafunctional), thiol equivalent 127 g / eq, CH3CH2SH: pKa 10.5).
[0279] [Chemical formula 20]
[0280]
[0281] B2-3: Multhiol Y-3 (manufactured by SC Organic Chemical Co., Ltd., aliphatic thiol (trifunctional), thiol equivalent 124 g / eq, CH3CH2SH: pKa 10.5).
[0282] [Chemical formula 21]
[0283]
[0284] B2-4: Karenz MT BD1 (manufactured by Showa Denko K.K., aliphatic thiol (difunctional), thiol equivalent 147 g / eq, CH3CH2SH: pKa 10.5).
[0285] [Chemical formula 22]
[0286]
[0287] B2-5: ASD (manufactured by Seika Corporation, aromatic amine (difunctional), amine equivalent 54.075 g / eq, C6H5NH2: pKa 28).
[0288] [Chemical formula 23]
[0289]
[0290] <Aliphatic amine compounds>
[0291] Isophoronediamine (manufactured by Fujifilm Wako Co., Ltd., aliphatic amine (difunctional), amine equivalent weight 42.575 g / eq, reference Et2NH: pKa 36).
[0292] <Anhydride>
[0293] Rikacid MH-700 (manufactured by Shin Nippon Chemical Co., Ltd., equivalent weight 163.5 g / eq).
[0294] pKa is determined by the following method.
[0295] (pKa)
[0296] For compounds whose pKa values are known in the literature (https: / / organicchemistrydata.org / hansreich / resources / pka / pka_data / pka-compilation-williams.pdf), the pKa values recorded in the literature were used. In addition, for compounds whose pKa values are not known in the above literature, active hydrogen compounds are described by structural formulas, and the pKa values of compounds with the same number of carbon atoms starting from the functional group with active hydrogen are used. It should be noted that the pKa of B1-3 uses the value recorded in Hazardous Substances Data Bank (HSDB): 513-PubChem (nih.gov).
[0297] 1-3. Curing catalyst
[0298] <Cationic Catalyst (C1)>
[0299] C1-1: SA1 (manufactured by SAN-APRO, phenolate of DBU, hot alkali catalyst).
[0300] C1-2: SA102 (manufactured by SAN-APRO, 2-ethylhexane salt of DBU, hot alkali catalyst).
[0301] C1-3: Tetramethylguanidine (manufactured by Tokyo Chemical Industry Co., Ltd., base catalyst).
[0302] C1-4: DBU (manufactured by Tokyo Chemical Industry Co., Ltd., diazabicycloundecene, base catalyst).
[0303] C1-5: TPP-MK (produced by Hokuko Chemical Industry Co., Ltd., tetraphenylphosphonium tetra-p-toluene borate, phosphorus-based curing accelerator).
[0304] C1-6: 2E4MZ (manufactured by Shikoku Chemicals Co., Ltd., 2-ethyl-4-methylimidazole, a general-purpose cationic catalyst).
[0305] <Catalyst (C2) that generates cations by reaction or light irradiation>
[0306] C2-1: DDA5 (dicyandiamide, latent catalyst).
[0307] C2-2: WPBG-266 (manufactured by Fujifilm Wako Co., Ltd., 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidinium 2-(3-benzoylphenyl)propionate, photobase catalyst).
[0308] C2-3: WPBG-300 (manufactured by Fujifilm Wako Co., Ltd., 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidinium n-butyltriphenylborate, photobase catalyst).
[0309] C2-4: 2-(9-oxobenzofluoren-2-yl)propanoic acid-1,5,7-triazabicyclo[4.4.0]dec-5-enyl salt (photobase catalyst).
[0310] 1-4. Sensitizer
[0311] Kayacure DETX-S (manufactured by Nippon Kayaku Co., Ltd., 2,4-diethylthioanthrone).
[0312] 2. Study on curing reactivity
[0313] <Preparation of Compositions 1 to 47>
[0314] The mass of the epoxy resin was set to 3 g, and the materials were uniformly stirred and mixed at the mixing ratios shown in Tables 1 to 3 using Awatori Rentaro (ARE-310) in a stirring mode at 2000 rpm for 30 seconds to prepare compositions 1 to 47.
[0315] <Evaluation>
[0316] The curing reactivity of the obtained composition was evaluated by the following method.
[0317] (Exothermic peak temperature obtained by DSC)
[0318] The obtained composition was placed in a 3.0 mg aluminum sample pan and subjected to differential scanning calorimetry (DSC) measurement. Specifically, a DSC-60 manufactured by Shimadzu Corporation was used to measure the exothermic peak temperature (thermosetting temperature) observed when the temperature was increased from room temperature (25° C.) at a rate of 20° C. / min.
[0319] Then, evaluation was performed according to the following criteria.
[0320] ⊚: The exothermic peak temperature in DSC measurement is lower than 199° C. (exothermic peak temperature of acid anhydride).
[0321] ○: The exothermic peak temperature in DSC measurement is 199°C or higher and lower than 250°C.
[0322] Δ: An exothermic peak was confirmed in DSC measurement, but the exothermic peak temperature was 250° C. or higher.
[0323] ×: No exothermic peak was confirmed in DSC measurement.
[0324] When it is ○ or more, the reactivity is judged to be good.
[0325] The evaluation results of compositions 1 to 13 are shown in Table 1, the evaluation results of compositions 14 to 29 are shown in Table 2, and the evaluation results of compositions 30 to 47 are shown in Table 3.
[0326] It should be noted that, as the curing type (method), the curing method using an active hydrogen compound (B1) is set to "1", the curing method using an active hydrogen compound (B2) and a cationic catalyst (C1) is set to "2", and the curing method using an active hydrogen compound (B2) and a catalyst (C2) that generates a cation by reaction, etc. is set to "3".
[0327] [Table 1]
[0328]
[0329] [Table 2]
[0330]
[0331] [Table 3]
[0332]
[0333] As shown in Tables 1 to 3, compositions 37 to 41 and 44 (Examples) containing an active hydrogen compound (B1) having a pKa of 10 or less, compositions 23, 25 to 29, 33, 34, 36 and 45 (Examples) using an active hydrogen compound (B2) having a pKa of more than 10 and a cationic catalyst (C1), compositions 14 to 20 and 24 (Examples) containing an active hydrogen compound (B2) and dicyandiamide, and compositions 30 to 32 and 35 (Examples) containing an active hydrogen compound (B2) and a photobase catalyst, although using alicyclic epoxy resins, showed curing reactivity equal to or better than that of a composition containing an acid anhydride curing agent (Comparative Example). In particular, except for compositions 24 and 45, the exothermic peak temperature was lower than the exothermic peak temperature of the acid anhydride, indicating good curing reactivity.
[0334] Among them, it can be seen that aliphatic thiols and aliphatic amines (active hydrogen compounds (B2)) have high pKa and low curing reactivity when used alone; while aromatic thiols (active hydrogen compounds (B1)) with low pKa also show good curing reactivity when used alone (comparison of compositions 37 to 41 with compositions 2 and 4).
[0335] It is also found that aliphatic thiol (active hydrogen compound (B2)) has a high pKa and low curing reactivity when used alone, but exhibits good curing reactivity when used in combination with the cationic catalyst (C1) (comparison between compositions 25 to 29 and composition 4).
[0336] It is also found that aliphatic thiol (active hydrogen compound (B2)) has a high pKa and low curing reactivity when used alone, but exhibits good curing reactivity when used in combination with dicyandiamide (catalyst (C2)) (comparison between composition 15 and composition 4).
[0337] In addition, it can be seen that good curing reactivity is shown by using a photobase catalyst (catalyst (C2)) in combination (comparison between composition 4 and compositions 30 to 32 and 35). Among them, the exothermic peak temperature after light irradiation is lower than the exothermic peak temperature before light irradiation. This shows that curability is further improved by light irradiation (refer to compositions 30 to 32 and 35).
[0338] 3. Quantification of Guanidine Amount
[0339] 3-1. Preparation of composition
[0340] <Preparation of Compositions R0 to R5>
[0341] The materials were uniformly stirred and mixed at the mixing ratio shown in Table 4 using a vacuum mixer Awatori Rentaro ARV-310P at 2000 rpm / 100 seconds and defoamed to prepare a composition.
[0342] <Preparation of Measurement Samples>
[0343] The compositions 14, 15, R0, R1, and R4 prepared above were cured by heating under the conditions shown in Table 4 to prepare cured product samples. The other compositions were used as samples as they were.
[0344] 3-2. Evaluation (crushing)
[0345] For the solidified sample, the blade of M22 was set in the universal grinder M20, and the solidified material crushed by hammer was put into the grinder under water cooling state, and the crushed material was put into the grinder for 1 minute, and the crushed material was put into the 60 mesh stainless steel mesh for sieving. The product passing through the 60 mesh screen was recovered, and the product remaining on the 60 mesh screen was put into M20 again, and the operation was repeated until the product passing through the screen reached 2g.
[0346] (extraction)
[0347] 10 g of water, which is 5 times the amount of the fine powder, was added, and the mixture was heated at 120° C. / 20 hours in a pressure vessel, cooled to room temperature, and then filtered using filter paper (5C).
[0348] (Ion chromatography determination)
[0349] The obtained extract or sample is weighed into a test tube, fixed to volume with water, dissolved or extracted with ultrasound for 10 minutes, and filtered with a membrane filter. The obtained solution is measured by ion chromatography. The measurement conditions are as follows. (Measurement conditions)
[0350] Device: TOSOH IC-2010.
[0351] Chromatographic column: Shodex IC YS-50 (125×4.6mm ID).
[0352] Short chromatographic column: Shodex IC YS-G (10×4.6mm ID).
[0353] Suppressor: No suppressor.
[0354] Eluent: 4 mM CH3SO3H.
[0355] Eluent flow rate: 1.0 mL / min.
[0356] Column temperature: 40℃.
[0357] Injection volume: 30μl.
[0358] Detector: Conductivity detector (CD).
[0359] The measurement results are shown in Figure 4 .
[0360] [Table 4]
[0361]
[0362] As shown in Table 4, guanidine was not detected from the compositions R1 to R3. In addition, only a very small amount of guanidine was detected from the cured product of the composition R0 and the composition R5.
[0363] On the other hand, guanidine was detected in an amount greater than or equal to the predetermined amount in the cured products of compositions 14, 15, and R4. This indicates that the aliphatic thiol compound (B2-1) reacts with dicyandiamide (C2-1) to produce guanidine.
[0364] 4. Study of refractive index
[0365] 4-1. Preparation of cured product
[0366] <Preparation of Cured Material 1>
[0367] The materials were uniformly stirred and mixed at the mixing ratio shown in Table 5 using a vacuum mixer Awatori Rentaro ARV-310P at 2000 rpm for 100 seconds and defoamed to prepare a composition.
[0368] The obtained composition was poured into a mold, heated at 90° C. for 3 hours, and then heated at 120° C. for 4 hours to be cured, thereby obtaining a cured product 1 having a thickness of 3 mm.
[0369] <Preparation of Cured Product 2 and Cured Product 3>
[0370] The materials were uniformly stirred and mixed at the mixing ratio shown in Table 5 using a vacuum mixer Awatori Rentaro ARV-310P at 2000 rpm for 100 seconds and defoamed to prepare a composition.
[0371] The obtained composition was poured into a mold, and cured by heating at 120° C. for 1 hour to obtain a cured product 2 and a cured product 3 having a thickness of 3 mm.
[0372] <Preparation of Cured Material 4>
[0373] The composition 23 prepared above was poured into a mold, and heated at 60° C. for 1 hour to be cured, thereby obtaining a cured product 4 .
[0374] <Preparation of Cured Material 5>
[0375] The composition 24 prepared above was poured into a mold, and cured by heating at 130° C. for 1 hour to obtain a cured product 5 having a thickness of 3 mm.
[0376] <Preparation of Cured Product 6 and Cured Product 7>
[0377] The materials were uniformly stirred and mixed at the mixing ratio shown in Table 5 using a vacuum mixer Awatori Rentaro ARV-310P at 2000 rpm for 100 seconds and defoamed to prepare a composition.
[0378] The obtained composition was poured into a mold, and cured by heating at 100° C. for 1 hour to obtain cured products 6 and 7 having a thickness of 3 mm.
[0379] 4-2. Evaluation
[0380] The refractive index of the cured products 1 to 7 prepared above was evaluated by the following method.
[0381] (Refractive Index)
[0382] The refractive index of the cured product was measured using Abbe Refractometer DR-A1-Plus at a wavelength of 589 nm. Monobromonaphthalene was used as the intermediate liquid.
[0383] The measurement results are shown in Table 5.
[0384] [Table 5]
[0385]
[0386] As shown in Table 5, it can be seen that the cured products 6 and 7 (Examples) of the composition containing an active hydrogen compound (B1) having a pKa of 10 or less, the cured product 4 (Example) of the composition using an active hydrogen compound (B2) having a pKa of more than 10 and a cationic catalyst, and the cured products 2, 3 and 5 (Example) of the composition containing an active hydrogen compound and dicyandiamide all have higher refractive indices than the cured product 1 (Comparative Example) of the composition containing an acid anhydride curing agent.
[0387] 5. Study on bending characteristics
[0388] 5-1. Preparation of cured product
[0389] <Preparation of Cured Products 1 to 5>
[0390] The cured products 1 to 5 prepared above were prepared.
[0391] <Preparation of Cured Products 8 to 10>
[0392] The materials were uniformly stirred and mixed at the mixing ratio shown in Table 6 using a vacuum mixer Awatori Rentaro ARV-310P at 2000 rpm for 100 seconds and defoamed to prepare a composition.
[0393] The obtained composition was poured into a mold, heated at 100° C. for 0.5 hour, and then further heated at 120° C. for 0.5 hour to be cured, thereby obtaining cured products 8 to 10 having a thickness of 3 mm.
[0394] 5-2. Evaluation
[0395] The bending properties of the cured products 1 to 5 and 8 to 10 prepared above were evaluated by the following method.
[0396] (Flexural modulus and flexural strength)
[0397] The obtained cured product was cut into a size of 80 mm×10 mm to prepare a test piece. Using the test piece, the flexural modulus, flexural strength, and strain rate were determined in accordance with the method of JIS K7171.
[0398] (Strain rate and yield point)
[0399] The presence or absence of the yield point of the test piece is determined based on the presence or absence of a point in the stress-strain curve where the stress does not increase but the strain increases.
[0400] The measurement results are shown in Table 6.
[0401] [Table 6]
[0402]
[0403] As shown in Table 6, it can be seen that any of the cured products 4 (Example) of the composition in which an active hydrogen compound having a pKa of more than 10 is used in combination with a cationic catalyst, and the cured products 2, 3, and 5 (Example) of the composition containing an active hydrogen compound and dicyandiamide have higher flexural strength and flexural elastic modulus than the cured product 1 (Comparative Example) of the composition containing an acid anhydride curing agent, and also have higher strain rate and yield point.
[0404] Furthermore, it is found that the flexural modulus and strain rate of the cured products 2 to 5 (Examples) are higher than those of the cured product 9 and the cured product 10 (Comparative Example) using an aromatic epoxy resin.
[0405] 6. Study on Thermoplasticity
[0406] 6-1. Preparation of Compositions 2-1 to 2-11
[0407] The components shown in Table 7 were blended in the blending ratios shown in the table and mixed under the following mixing conditions 1 or 2.
[0408] (Mixing condition 1)
[0409] The mixture was uniformly stirred and mixed at 2000 rpm for 100 seconds using a vacuum mixer Awatori Rentaro (ARV-310P), and then defoamed to prepare a composition.
[0410] (Mixed condition 2)
[0411] The mixture was uniformly stirred and mixed using a vacuum mixer Awatori Rentaro (ARE-310) at 2000 rpm in stirring mode for 30 seconds to prepare a composition.
[0412] It should be noted that compositions 2-2, 2-3, 2-5, 2-6, 2-8 and 2-9 correspond to the above-mentioned compositions 34, 35, 38, 39, 44 and 47, respectively.
[0413] 6-2. Evaluation
[0414] The obtained compositions were evaluated as follows.
[0415] 6-2-1. Viscosity of composition
[0416] The viscosity (25° C., 5 rpm, 30 seconds) of each composition prepared under mixing condition 1 was measured using a cone-plate viscometer (TVE-35H, cone rotor: 3°×R9.7, manufactured by Toki Sangyo).
[0417] 6-2-2. Evaluation of cured product
[0418] Thermoplasticity and self-healing properties (appearance, bending test) of the cured products of the compositions prepared under mixing condition 2 were evaluated by the following methods. The cured products of compositions 2 to 6 were further subjected to TOF-MS analysis.
[0419] (1) Thermoplastic
[0420] The obtained composition was poured into a mold frame with a 1 mm thick silicone rubber sandwiched between two glass slides (manufactured by Matsunami Glass Co., Ltd., Matsunami glass slide model S7214), and heated under the curing conditions shown in the table to cure it to obtain a cured product with a thickness of 1 mm. It should be noted that for curing condition 2 of composition 2-3, the composition was poured into the mold frame, irradiated with a UV irradiator of a high-pressure mercury lamp (manufactured by EYEGRAPHIC Co., Ltd., (registered trademark) ECS-4011GX) under the condition of an irradiation amount of 9000 mJ, and then heated at 120° C. for 1 hour to obtain a cured product with a thickness of 1 mm.
[0421] The obtained cured product was put into an oven heated to 120° C. in a state of standing up with clips, and after heating at 120° C. for 1 hour, the state of the standing cured product was visually observed to evaluate thermoplasticity. Then, the evaluation was performed according to the following criteria.
[0422] 4: The solidified material pours out, showing thermoplasticity.
[0423] 3: The cured product can be taken out of the mold while maintaining the same shape as the mold box. However, if the cured product is left standing for a certain period of time before heating at 120°C for 1 hour, it will fall over (curing is not sufficient, but thermoplasticity is shown).
[0424] 2: Thickened, but cannot be removed from the mold frame (uncured).
[0425] 1: Maintains an upright state and does not show thermoplasticity.
[0426] (2) Self-healing properties - appearance
[0427] The solidified product obtained in the same manner as in the above (1) was placed in a freezer at -30°C from each solidification temperature in a state sandwiched between slides to generate cracks. In the case where no cracks were generated, the solidified product was bent to such an extent that the slide did not break to generate cracks. Then, the state of the cracks was visually observed after the solidified product with cracks generated at room temperature was heated at 120°C for 5 minutes. Then, the evaluation was performed based on the following criteria.
[0428] 3: The crack disappears.
[0429] 2: No cracks even when bent.
[0430] 1: Remain hard and cracks do not disappear.
[0431] (3) Self-repairability-bending test (preparation of evaluation samples)
[0432] Composition A was prepared by mixing and defoaming with a vacuum mixer Awatori Rentaro (ARV-310P) at a stirring mode of 2000 rpm / 180 seconds with 100 parts by mass of Celloxide 2021P (Dacel), 80 parts by mass of TS-G (Shikoku Chemical), and 1 part by mass of DDA5. The obtained composition A was poured into a mold and heated at 120°C for 1 hour to obtain two cured products with a thickness of 1 mm.
[0433] On the other hand, the composition B was prepared by mixing and defoaming the mixture at the mixing ratio of composition 2-6 or 8 using a vacuum mixer Awatori Rentaro (ARV-310P) at a stirring mode of 2000 rpm / 100 seconds.
[0434] Then, the composition B prepared above was poured between the two cured products prepared above, and heated under the conditions described in Table 7. Thus, a cured product having a three-layer structure (cured product A (for outer wall) / cured product B (evaluation object) / cured product A (for outer wall)) with a total thickness of 3 mm was obtained.
[0435] (Bending test)
[0436] The obtained cured product was subjected to a bending test according to JIS K 6911. That is, a cured product with a thickness of 3 mm was cut into a size of 80×10 mm as a test piece. Using the test piece, the support point spacing was set to 50 mm, the test speed was set to 1.5 mm / min, and a three-point bending test was performed according to the method of JIS K 6911 to measure the bending elastic modulus. The bending elastic modulus was calculated by the following calculation formula.
[0437] Elastic modulus (N / mm 2 ) = slope × support distance / cross-sectional area of the test piece
[0438] The slope is calculated by the least squares method using all data between the two points where the test force is 10N and 20N, with the test force on the vertical axis and the displacement on the horizontal axis.
[0439] After the cured product was cut into a size for the bending test, transparent tape was attached only to the four sides of the test piece, which were the thickness sides, to prevent the inner layer structure from slipping due to the impact during the test.
[0440] The test was carried out in the following order 1 to 9. After heating, the test was performed after cooling at room temperature for 1 hour.
[0441] 1. Initial heating: Place in an oven heated to 120°C for 10 minutes (to repair cracks that occurred when cutting into test piece size).
[0442] 2. Initial measurement: bending test.
[0443] 3. Determination at failure: bending test.
[0444] 4.120℃ repair: Put in an oven heated to 120℃ for 10 minutes.
[0445] 5.120℃-Determination of elastic modulus: bending test.
[0446] 6.100℃ repair: Put in an oven heated to 100℃ for 10 minutes.
[0447] 7.100℃ measurement: bending test.
[0448] 8.140℃ repair: Put in an oven heated to 140℃ for 10 minutes.
[0449] 9.140℃ measurement: bending test.
[0450] The repair rate (%) at each temperature was evaluated based on the following formula.
[0451] Repair rate (%) = (measured value at each temperature - measured value at the time of destruction) / (initial measured value - measured value at the time of destruction) × 100
[0452] In addition, the measured value refers to the bending elastic modulus measured by a bending test.
[0453] When the above-mentioned repair rate is positive, it means that self-repairing property is exhibited, and the temperature at which the above-mentioned repair rate becomes positive is regarded as the temperature at which self-repairing can be performed. It should be noted that when the above-mentioned repair rate is negative, it is recorded as 0%, indicating that self-repairing property is not exhibited.
[0454] (4)TOF-MS analysis
[0455] The structure of the cured product of Composition 2-6 was analyzed by TOF-MS analysis.
[0456] Specifically, 10 mg of the solidified material was weighed, 5 mL of chloroform was added, and ultrasonic treatment was performed for 10 minutes. 1 μL of the sample solution was applied to a FD emitter (Field Desorption emitter), and the measurement was performed under the following conditions using JMS-T100GCV manufactured by JEOL Ltd. (JEOL).
[0457] Sample: Diluted in chloroform.
[0458] Ionization mode: FD+.
[0459] Analysis m / z range: 29.00~3000.00.
[0460] The evaluation results of compositions 2-1 to 2-11 are shown in Table 7. Among them, the appearance of the cured product obtained from composition 2-6 before heating is shown in Table 7. Figure 1 A, the appearance after heating is shown in Figure 1 B; The appearance of the cured product obtained from composition 2-7 before heating is shown in Figure 2 A, the appearance after heating is shown in Figure 2 B.
[0461] In addition, the reaction mechanism of composition 2-6 is shown in Figure 3 A, the TOF-MS spectrum of its solidified product is shown in Figure 3 B. Table 8 shows the evaluation results of (3) self-repairability-bending test of Composition 2-6 and Composition 2-8.
[0462] It should be noted that in Table 7, as the curing type (method), the curing method using an active hydrogen compound (B1) is set to "1", the curing method using an active hydrogen compound (B2) and a cationic catalyst (C1) is set to "2", and the curing method using an active hydrogen compound (B2) and a catalyst (C2) that generates a cation by reaction, etc. is set to "3".
[0463] [Table 7]
[0464]
[0465] [Table 8]
[0466]
[0467] As shown in Table 7, the cured products of compositions 2-9 and 2-11 did not soften even when heated at 120°C for 1 hour, indicating that they did not exhibit thermoplasticity. In addition, the cured products heated at 120°C for 5 minutes did not soften but remained hard, and the cracks did not disappear. This indicates that they did not have self-healing properties.
[0468] In contrast, the cured products of compositions 2-1 to 2-8 softened when heated at 120°C for 1 hour, showing thermoplasticity. In addition, the cured products softened after heating at 120°C for 5 minutes, and the cracks disappeared. It can be seen that they have self-repairing properties (see Table 7). In addition, for compositions 2-6 and 8, the repair rate increased, especially at 120°C and 140°C, showing good self-repairing properties (see Table 8).
[0469] In addition, as mentioned above, in the curing system using anhydride, the epoxy group of the alicyclic epoxy resin will open the ring to form an oxygen anion (-O - ), so it is easy to react with other alicyclic epoxy resins (not only with active hydrogen compounds), thereby forming three-dimensional crosslinking. In contrast, in the present invention, after the epoxy group of the alicyclic epoxy resin reacts with the active hydrogen compound, it will be cationized (this time H + ) reacts to become -OH, so it will not react with other alicyclic epoxy resins, but only react with active hydrogen compounds. Therefore, the difference between the structure of the conventional reaction and the structure of the present invention is that the oxygen derived from the epoxy group is -O - It is still -OH, so there will be a weight difference of 1 H. Therefore, in the case of -O - When the reaction is carried out, the weight of 1 H is subtracted from the molecular weight of the epoxy resin + active hydrogen compound; when the reaction is carried out with -OH, the molecular weight of the epoxy resin + active hydrogen compound remains unchanged, and the molecular weight is increased.
[0470] In the combination of composition 2-6, the molecular weight of epoxy resin + active hydrogen compound is as follows: Figure 3 A shows 444.1. Figure 3 In the TOF-MS spectrum of Example 6 shown in B, as main peaks, at 444.1143, 888.2360, and 1332.3430, the molecular weight of a unit having a molecular weight of 444.1 containing -OH can be confirmed. In addition, it can be seen that the peak of A-2 (molecular weight 194.1) derived from the alicyclic epoxy resin (A) and the peak of B1-1 (molecular weight 249.9) derived from the active hydrogen compound (B1) appear alternately (refer to Figure 3). That is, a repeating structure (molecular weight 444.1) in which alicyclic epoxy resin (A)-thiol compound (B1)-... was bonded in the order was detected. This shows that the assumed reaction, that is, linear polymerization of alicyclic epoxy resin and thiol compound, occurred.
[0471] 7. Research on Mixability
[0472] (1) Preparation of test pieces
[0473] Using a mixing device Labo Plastomill [roll mixer R30] (manufactured by Toyo Seiki Co., Ltd.), 14.25 g of PP (MA3) (Novatec PP manufactured by Polypropylene Co., Ltd., general injection molding grade, polypropylene resin) and 0.75 g of the cured product (thermoplastic resin) of composition 2-6 were melt-mixed at 180°C for 10 minutes, and then press-molded at 180°C to obtain a sample sheet with a thickness of 0.31 mm.
[0474] (2) Evaluation method
[0475] A portion of the obtained sample piece was cut into strips with a scraper. A crack was formed in the center beforehand, and the strips were cut in liquid nitrogen. The strips were placed on a sample stand with a carbon tape attached with the observation side facing upward, and metal deposition with osmium was performed.
[0476] Then, the surface of the sample piece after metal evaporation was subjected to SEM observation and energy dispersion spectrum (EDS) analysis, and image analysis was performed. In the image analysis, the S mapping image of the sample at 3k was used to implement it for 3 fields of view. It should be noted that the area, major diameter, and average neighbor spacing of the spherical particles in Table 9 show the maximum value (Max), minimum value (Min), median value (Med), standard deviation (SD), and average value (Ave) when measuring 123 spherical particles.
[0477] The results of SEM observation of the surface of the sample piece of composition 2-6 are shown in Figure 4 A, the EDX analysis results are shown in Figure 4 B and Figure 4 C. In addition, the image analysis results are shown in Table 9. Figure 4 B is a mapping image in which the portion where the carbon element (C) is detected (continuous phase) is displayed in gray. Figure 4 C is a mapping image in which the portion (dispersed phase) where sulfur element (S) is detected is displayed in gray.
[0478] [Table 9]
[0479]
[0480] As shown in the EDS analysis results ( Figure 4 B and Figure 4 As shown in Figure C), spherical particles (dispersed phase) containing sulfur element (S) derived from the cured product (thermoplastic resin) of the above composition were observed to be well dispersed in the continuous phase of PP as the matrix resin. The size of the spherical particles was about several hundred nanometers to 2 μm.
[0481] Furthermore, as shown in Table 9, it can be seen that the spherical particles of the thermoplastic resin have small areas, major diameters, and average neighbor distances, and are well dispersed.
[0482] This shows that the thermoplastic resin obtained by curing the curable composition containing the bifunctional epoxy resin (A') and the bifunctional active hydrogen compound (B') is well dispersed in the matrix resin and is suitable as a masterbatch.
[0483] This application claims priority based on Japanese Patent Application No. 2022-138414 filed on August 31, 2022 and Japanese Patent Application No. 2022-138424 filed on August 31, 2022. The contents described in the application specification and drawings are all incorporated herein by reference.
[0484] Industrial Applicability
[0485] According to the present invention, there can be provided a curable composition which exhibits good curing reactivity even when containing a large amount of alicyclic epoxy resin.
Claims
1. A curable composition comprising an alicyclic epoxy resin (A) and an active hydrogen compound (B1) having a pKa of 10 or less.
2. The curable composition according to claim 1, wherein The active hydrogen compound (B1) includes an aromatic thiol compound.
3. The curable composition according to claim 1, wherein The alicyclic epoxy resin (A) is a difunctional alicyclic epoxy resin (A'), The active hydrogen compound (B1) having a pKa of 10 or less is a bifunctional active hydrogen compound (B1′) having a pKa of 10 or less.
4. A curable composition comprising an alicyclic epoxy resin (A), an active hydrogen compound (B2) having a pKa of more than 10, and a cationic catalyst (C1), wherein: The content ratio of the active hydrogen compound (B2) relative to 100 parts by mass of the alicyclic epoxy resin (A) is 40 to 200 in terms of mass ratio.
5. The curable composition according to claim 4, wherein The active hydrogen compound (B2) includes aliphatic thiol compounds.
6. A curable composition comprising a difunctional alicyclic epoxy resin (A'), a difunctional active hydrogen compound (B2') having a pKa of more than 10, and a cationic catalyst (C1).
7. A curable composition comprising an alicyclic epoxy resin (A), an active hydrogen compound (B2) having a pKa of more than 10, and a catalyst (C2) that generates a cation by reaction with the active hydrogen compound (B2) or by light irradiation.
8. The curable composition according to claim 7, wherein The active hydrogen compound (B2) includes aliphatic thiol compounds.
9. The curable composition according to claim 7, wherein The catalyst (C2) is a catalyst that generates a cationic species by reacting with the active hydrogen compound (B2). The catalyst (C2) comprises dicyandiamide.
10. The curable composition according to claim 7, wherein The alicyclic epoxy resin (A) is a difunctional alicyclic epoxy resin (A'), The active hydrogen compound (B2) having a pKa of more than 10 is a difunctional active hydrogen compound (B2′) having a pKa of more than 10. 11 . A cured product, which is a cured product of the curable composition according to claim 1 . 12 . A cured product, which is a cured product of the curable composition according to claim 4 . 13 . A cured product, which is a cured product of the curable composition according to claim 7 .
14. A method for producing a solidified product, comprising: A step of reacting an active hydrogen compound (B2) with dicyandiamide under heating to obtain a composition containing guanidine; as well as A step of reacting the composition with an alicyclic epoxy resin (A) under heating to obtain a cured product of the curable composition containing the alicyclic epoxy resin (A).
15. A thermoplastic resin comprising a structural unit derived from a difunctional alicyclic epoxy resin (A') and a structural unit derived from a difunctional active hydrogen compound (B').
Citation Information
Patent Citations
Recyclable epoxy resin composition
JP2001348419A
Method for molding fiber-reinforced thermoplastic resin
JP2006321897A
Light emitting diode
JP2007109915A
Resin composition for sealing optical semiconductor
JP2010053199A
adhesive
JP2019194322A